Gadolinium tissue deposition in the periodontal ligament of mice with reduced renal function exposed to Gd-based contrast agents. - Delfino, Riccarda; Biasotto, Matteo; Candido, Riccardo; Altissimo, Matteo; Stebel, Marco; Salomè, Murielle; van Elteren, Johannes T; Vogel Mikuš, Katarina; Zennaro, Cristina; Šala, Martin; Addobbati, Riccardo; Tromba, Giuliana; et al. (Toxicol Lett, 2019)
Gadolinium deposition in tissue is linked to nephrogenic systemic fibrosis (NSF): a rare disorder occurring in patients with severe chronic kidney disease and associated with administration of Gd-based contrast agents (GBCAs) for Magnetic Resonance Imaging (MRI). It is suggested that the GBCAs prolonged permanence in blood in these patients may result in a Gd precipitation in peripheral or central organs, where it initiates a fibrotic process. In this study we investigated new sites of retention/precipitation of Gd in a mouse model of renal disease (5/6 nephrectomy) receiving two doses (closely after each other) of a linear GBCA. Two commercial GBCAs (Omniscan® and Magnevist®) were administered at doses slightly higher than those used in clinical practice (0.7 mmol/kg body weight, each). The animals were sacrificed one month after the last administration and the explanted organs (kidney, liver, femur, dorsal skin, teeth) were analysed by X-ray fluorescence (XRF) at two synchrotron facilities. The XRF analysis with a millimetre-sized beam at the SYRMEP beamline (Elettra, Italy) produced no detectable levels of Gd in the examined tissues, with the notable exception of the incisors of the nephrectomised mice. The XRF analyses at sub-micron resolution performed at ID21 (ESRF, France) allowed to clearly localize Gd in the periodontal ligaments of teeth both from Omniscan® and Magnevist® treated nephrectomised mice. The latter results were further confirmed by laser ablation inductively coupled plasma mass spectrometry (LA-ICP-MS). The study prompts that prolonged permanence of GBCAs in blood may result in Gd retention in this particular muscular tissue, opening possibilities for diagnostic applications at this level when investigating Gd-related toxicities.
Keywords: Animals; Contrast Media; Disease Models, Animal; Dose-Response Relationship, Drug; Female; Gadolinium; Gadolinium DTPA; Magnetic Resonance Imaging; Mice; Nephrogenic Fibrosing Dermopathy; Periodontal Ligament; Renal Insufficiency; Tissue Distribution

Global, regional, and national burden of traumatic brain injury and spinal cord injury, 1990-2016: a systematic analysis for the Global Burden of Disease Study 2016. (Lancet Neurol, 2019)
BACKGROUND: Traumatic brain injury (TBI) and spinal cord injury (SCI) are increasingly recognised as global health priorities in view of the preventability of most injuries and the complex and expensive medical care they necessitate. We aimed to measure the incidence, prevalence, and years of life lived with disability (YLDs) for TBI and SCI from all causes of injury in every country, to describe how these measures have changed between 1990 and 2016, and to estimate the proportion of TBI and SCI cases caused by different types of injury. METHODS: We used results from the Global Burden of Diseases, Injuries, and Risk Factors (GBD) Study 2016 to measure the global, regional, and national burden of TBI and SCI by age and sex. We measured the incidence and prevalence of all causes of injury requiring medical care in inpatient and outpatient records, literature studies, and survey data. By use of clinical record data, we estimated the proportion of each cause of injury that required medical care that would result in TBI or SCI being considered as the nature of injury. We used literature studies to establish standardised mortality ratios and applied differential equations to convert incidence to prevalence of long-term disability. Finally, we applied GBD disability weights to calculate YLDs. We used a Bayesian meta-regression tool for epidemiological modelling, used cause-specific mortality rates for non-fatal estimation, and adjusted our results for disability experienced with comorbid conditions. We also analysed results on the basis of the Socio-demographic Index, a compound measure of income per capita, education, and fertility. FINDINGS: In 2016, there were 27·08 million (95% uncertainty interval [UI] 24·30-30·30 million) new cases of TBI and 0·93 million (0·78-1·16 million) new cases of SCI, with age-standardised incidence rates of 369 (331-412) per 100 000 population for TBI and 13 (11-16) per 100 000 for SCI. In 2016, the number of prevalent cases of TBI was 55·50 million (53·40-57·62 million) and of SCI was 27·04 million (24·98-30·15 million). From 1990 to 2016, the age-standardised prevalence of TBI increased by 8·4% (95% UI 7·7 to 9·2), whereas that of SCI did not change significantly (-0·2% [-2·1 to 2·7]). Age-standardised incidence rates increased by 3·6% (1·8 to 5·5) for TBI, but did not change significantly for SCI (-3·6% [-7·4 to 4·0]). TBI caused 8·1 million (95% UI 6·0-10·4 million) YLDs and SCI caused 9·5 million (6·7-12·4 million) YLDs in 2016, corresponding to age-standardised rates of 111 (82-141) per 100 000 for TBI and 130 (90-170) per 100 000 for SCI. Falls and road injuries were the leading causes of new cases of TBI and SCI in most regions. INTERPRETATION: TBI and SCI constitute a considerable portion of the global injury burden and are caused primarily by falls and road injuries. The increase in incidence of TBI over time might continue in view of increases in population density, population ageing, and increasing use of motor vehicles, motorcycles, and bicycles. The number of individuals living with SCI is expected to increase in view of population growth, which is concerning because of the specialised care that people with SCI can require. Our study was limited by data sparsity in some regions, and it will be important to invest greater resources in collection of data for TBI and SCI to improve the accuracy of future assessments. FUNDING: Bill & Melinda Gates Foundation.

Gene discovery and polygenic prediction from a genome-wide association study of educational attainment in 1.1 million individuals. - Lee, James J; Wedow, Robbee; Okbay, Aysu; Kong, Edward; Maghzian, Omeed; Zacher, Meghan; Nguyen-Viet, Tuan Anh; Bowers, Peter; Sidorenko, Julia; Karlsson Linnér, Richard; Fontana, Mark Alan; Kundu, Tushar; et al. (Nat Genet, 2018)
Here we conducted a large-scale genetic association analysis of educational attainment in a sample of approximately 1.1 million individuals and identify 1,271 independent genome-wide-significant SNPs. For the SNPs taken together, we found evidence of heterogeneous effects across environments. The SNPs implicate genes involved in brain-development processes and neuron-to-neuron communication. In a separate analysis of the X chromosome, we identify 10 independent genome-wide-significant SNPs and estimate a SNP heritability of around 0.3% in both men and women, consistent with partial dosage compensation. A joint (multi-phenotype) analysis of educational attainment and three related cognitive phenotypes generates polygenic scores that explain 11-13% of the variance in educational attainment and 7-10% of the variance in cognitive performance. This prediction accuracy substantially increases the utility of polygenic scores as tools in research.

Genetic analysis of over 1 million people identifies 535 new loci associated with blood pressure traits. - Evangelou, Evangelos; Warren, Helen R; Mosen-Ansorena, David; Mifsud, Borbala; Pazoki, Raha; Gao, He; Ntritsos, Georgios; Dimou, Niki; Cabrera, Claudia P; Karaman, Ibrahim; Ng, Fu Liang; Evangelou, Marina; et al. (Nat Genet, 2018)
High blood pressure is a highly heritable and modifiable risk factor for cardiovascular disease. We report the largest genetic association study of blood pressure traits (systolic, diastolic and pulse pressure) to date in over 1 million people of European ancestry. We identify 535 novel blood pressure loci that not only offer new biological insights into blood pressure regulation but also highlight shared genetic architecture between blood pressure and lifestyle exposures. Our findings identify new biological pathways for blood pressure regulation with potential for improved cardiovascular disease prevention in the future.

Genetic profile of patients with early onset inflammatory bowel disease. - Girardelli, Martina; Basaldella, Federica; Paolera, Sara Della; Vuch, Josef; Tommasini, Alberto; Martelossi, Stefano; Crovella, Sergio; Bianco, Anna Monica (Gene, 2018)
Inflammatory Bowel disease (IBD) is a widespread pathological condition with clinical heterogeneity and with different levels of severity. Although IBD usually occurs in young adults, onset in childhood and infancy are described in patients within the 10th and second year of age. By genome-wide association studies and meta-analysis, several genetic loci have been identified associated with an increased risk of developing IBD in Western populations with variants that may alter the normal mucosal immunity in the gastrointestinal tract. The clinical complexity and the heterogeneity of the IBD phenotype probably reflect the presence of genetic heterogeneity where different genes or combinations of them may be involved, together with environmental factors. We hypothesized that patients with early onset IBD could have either more severe genetic variants in genes associated with IBD or multiple variants in different genes. Under the multifactorial diseases is crucial to consider the small contribution of a single variant in all not only to other small variations in the same gene but also in different genes belonging to the same pathway. We performed direct gene sequencing looking for 94 variations in NOD2, ATG16L1, IL23R, IL10R, IL10 and XIAP genes previously shown as correlated with IBD both in multifactorial and in Mendelian models. All variants identified are known in literature as being associated with IBD except for three variants in the genes NOD2, IL10 and IL10RB that even though present in online databases have never been involved in association studies on IBD patients. Moreover, we coupled genetic variants identification with an accurate "in silico" analysis to verify their predictive impact on the protein structure and function. The in-silico prediction of these variants results as benign therefore even if they exhibit a very low frequency in control population being benign, they cannot be considered pathogenic as monogenic disease but fall within the multifactorial range. The variants identified in our study partially reflect the association data described in the literature but there are no significant differences with the onset of disease (VEO vs EO-IBD).
Keywords: Age of Onset; Autophagy-Related Proteins; Child; Child, Preschool; Computer Simulation; Female; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Infant; Inflammatory Bowel Diseases; Interleukin-10; Male; Nod2 Signaling Adaptor Protein; Polymorphism, Single Nucleotide; Receptors, Interleukin; Receptors, Interleukin-10; Sequence Analysis, DNA; X-Linked Inhibitor of Apoptosis Protein

A genetic variant of NLRP1 gene is associated with asbestos body burden in patients with malignant pleural mesothelioma. - Crovella, S; Moura, R R; Cappellani, S; Celsi, F; Trevisan, E; Schneider, M; Brollo, A; Nicastro, E M; Vita, F; Finotto, L; Zabucchi, G; Borelli, V (J Toxicol Environ Health A, 2018)
The presence of asbestos bodies (ABs) in lung parenchyma is considered a histopathologic hallmark of past exposure to asbestos fibers, of which there was a population of longer fibers. The mechanisms underlying AB formation are complex, involving inflammatory responses and iron (Fe) metabolism. Thus, the responsiveness to AB formation is variable, with some individuals appearing to be poor AB formers. The aim of this study was to disclose the possible role of genetic variants of genes encoding inflammasome and iron metabolism proteins in the ability to form ABs in a population of 81 individuals from North East Italy, who died after having developed malignant pleural mesothelioma (MPM). This study included 86 genetic variants distributed in 10 genes involved in Fe metabolism and 7 genetic variants in two genes encoding for inflammasome molecules. Genotypes/haplotypes were compared according to the number of lung ABs. Data showed that the NLRP1 rs12150220 missense variant (H155L) was significantly correlated with numbers of ABs in MPM patients. Specifically, a low number of ABs was detected in individuals carrying the NLRP1 rs12150220 A/T genotype. Our findings suggest that the NLRP1 inflammasome might contribute in the development of lung ABs. It is postulated that the NLRP1 missense variant may be considered as one of the possible host genetic factors contributing to individual variability in coating efficiency, which needs to be taken when assessing occupational exposure to asbestos.

Genome Analyses of >200,000 Individuals Identify 58 Loci for Chronic Inflammation and Highlight Pathways that Link Inflammation and Complex Disorders. - Ligthart, Symen; Vaez, Ahmad; Võsa, Urmo; Stathopoulou, Maria G; de Vries, Paul S; Prins, Bram P; van der Most, Peter J; Tanaka, Toshiko; Naderi, Elnaz; Rose, Lynda M; Wu, Ying; Karlsson, Robert; et al. (Am J Hum Genet, 2018)
C-reactive protein (CRP) is a sensitive biomarker of chronic low-grade inflammation and is associated with multiple complex diseases. The genetic determinants of chronic inflammation remain largely unknown, and the causal role of CRP in several clinical outcomes is debated. We performed two genome-wide association studies (GWASs), on HapMap and 1000 Genomes imputed data, of circulating amounts of CRP by using data from 88 studies comprising 204,402 European individuals. Additionally, we performed in silico functional analyses and Mendelian randomization analyses with several clinical outcomes. The GWAS meta-analyses of CRP revealed 58 distinct genetic loci (p < 5 × 10). After adjustment for body mass index in the regression analysis, the associations at all except three loci remained. The lead variants at the distinct loci explained up to 7.0% of the variance in circulating amounts of CRP. We identified 66 gene sets that were organized in two substantially correlated clusters, one mainly composed of immune pathways and the other characterized by metabolic pathways in the liver. Mendelian randomization analyses revealed a causal protective effect of CRP on schizophrenia and a risk-increasing effect on bipolar disorder. Our findings provide further insights into the biology of inflammation and could lead to interventions for treating inflammation and its clinical consequences.

Genome-wide association meta-analysis highlights light-induced signaling as a driver for refractive error. - Tedja, Milly S; Wojciechowski, Robert; Hysi, Pirro G; Eriksson, Nicholas; Furlotte, Nicholas A; Verhoeven, Virginie J M; Iglesias, Adriana I; Meester-Smoor, Magda A; Tompson, Stuart W; Fan, Qiao; Khawaja, Anthony P; Cheng, Ching-Yu; et al. (Nat Genet, 2018)
Refractive errors, including myopia, are the most frequent eye disorders worldwide and an increasingly common cause of blindness. This genome-wide association meta-analysis in 160,420 participants and replication in 95,505 participants increased the number of established independent signals from 37 to 161 and showed high genetic correlation between Europeans and Asians (>0.78). Expression experiments and comprehensive in silico analyses identified retinal cell physiology and light processing as prominent mechanisms, and also identified functional contributions to refractive-error development in all cell types of the neurosensory retina, retinal pigment epithelium, vascular endothelium and extracellular matrix. Newly identified genes implicate novel mechanisms such as rod-and-cone bipolar synaptic neurotransmission, anterior-segment morphology and angiogenesis. Thirty-one loci resided in or near regions transcribing small RNAs, thus suggesting a role for post-transcriptional regulation. Our results support the notion that refractive errors are caused by a light-dependent retina-to-sclera signaling cascade and delineate potential pathobiological molecular drivers.

Genome-wide association meta-analysis of individuals of European ancestry identifies new loci explaining a substantial fraction of hair color variation and heritability. - Hysi, Pirro G; Valdes, Ana M; Liu, Fan; Furlotte, Nicholas A; Evans, David M; Bataille, Veronique; Visconti, Alessia; Hemani, Gibran; McMahon, George; Ring, Susan M; Smith, George Davey; Duffy, David L; et al. (Nat Genet, 2018)
Hair color is one of the most recognizable visual traits in European populations and is under strong genetic control. Here we report the results of a genome-wide association study meta-analysis of almost 300,000 participants of European descent. We identified 123 autosomal and one X-chromosome loci significantly associated with hair color; all but 13 are novel. Collectively, single-nucleotide polymorphisms associated with hair color within these loci explain 34.6% of red hair, 24.8% of blond hair, and 26.1% of black hair heritability in the study populations. These results confirm the polygenic nature of complex phenotypes and improve our understanding of melanin pigment metabolism in humans.

A genome-wide association study identifies an association between variants in EFCAB4B gene and periodontal disease in an Italian isolated population. - Bevilacqua, Lorenzo; Navarra, Chiara O; Pirastu, Nicola; Lenarda, Roberto Di; Gasparini, Paolo; Robino, Antonietta (J Periodontal Res, 2018)
BACKGROUND AND OBJECTIVE: Periodontitis in one of the most prevalent dental diseases. Despite numerous studies have investigated its aetiopathogenetic factors, few works have focused on its genetic predisposition and most of them took into account only candidate genes. Therefore, we conducted a Genome Wide Association Study in an Italian isolated population aimed at uncovering genetic variants that predispose to this disorder. METHODS: Diagnosis of chronic periodontitis was made following the criteria of the American Academy of Periodontology. Patients with chronic periodontitis were grouped into different categories: slight, severe, localized and generalized. A control group composed by people without signs of periodontitis or gingivitis was defined. DNA was genotyped using 370k Illumina chips. Linear mixed model regression was used to test the association between each single nucleotide polymorphism (SNP) (independent variable) and the periodontitis status (dependent variable), controlling for confounders sex, age and smoking. The genomic kinship matrix was also used as random effect. RESULTS: Four SNPs on the gene EFCAB4B resulted significantly associated to localized periodontitis (P < 5 × 10 ), with the best hit on the rs242016 SNP (P = 1.5 × 10 ). CONCLUSION: We have identified a novel significant association between the EFCAB4B gene and localized periodontitis. These results open a new perspective in the understanding of genetic factors contributing to this common disorder.
Keywords: Adolescent; Adult; Aged; Aged, 80 and over; Calcium-Binding Proteins; Chronic Periodontitis; DNA; Female; Genetic Predisposition to Disease; Genome-Wide Association Study; Genotype; Humans; Italy; Male; Middle Aged; Polymorphism, Single Nucleotide; Regression Analysis; Young Adult

A genome-wide association study of corneal astigmatism: The CREAM Consortium. - Shah, Rupal L; Li, Qing; Zhao, Wanting; Tedja, Milly S; Tideman, J Willem L; Khawaja, Anthony P; Fan, Qiao; Yazar, Seyhan; Williams, Katie M; Verhoeven, Virginie J M; Xie, Jing; Wang, Ya Xing; et al. (Mol Vis, 2018)
Purpose: To identify genes and genetic markers associated with corneal astigmatism. Methods: A meta-analysis of genome-wide association studies (GWASs) of corneal astigmatism undertaken for 14 European ancestry (n=22,250) and 8 Asian ancestry (n=9,120) cohorts was performed by the Consortium for Refractive Error and Myopia. Cases were defined as having >0.75 diopters of corneal astigmatism. Subsequent gene-based and gene-set analyses of the meta-analyzed results of European ancestry cohorts were performed using VEGAS2 and MAGMA software. Additionally, estimates of single nucleotide polymorphism (SNP)-based heritability for corneal and refractive astigmatism and the spherical equivalent were calculated for Europeans using LD score regression. Results: The meta-analysis of all cohorts identified a genome-wide significant locus near the platelet-derived growth factor receptor alpha () gene: top SNP: rs7673984, odds ratio=1.12 (95% CI:1.08-1.16), p=5.55×10. No other genome-wide significant loci were identified in the combined analysis or European/Asian ancestry-specific analyses. Gene-based analysis identified three novel candidate genes for corneal astigmatism in Europeans-claudin-7 (), acid phosphatase 2, lysosomal (), and TNF alpha-induced protein 8 like 3 (). Conclusions: In addition to replicating a previously identified genome-wide significant locus for corneal astigmatism near the gene, gene-based analysis identified three novel candidate genes, , , and , that warrant further investigation to understand their role in the pathogenesis of corneal astigmatism. The much lower number of genetic variants and genes demonstrating an association with corneal astigmatism compared to published spherical equivalent GWAS analyses suggest a greater influence of rare genetic variants, non-additive genetic effects, or environmental factors in the development of astigmatism.
Keywords: Acid Phosphatase; Asian Continental Ancestry Group; Astigmatism; Claudins; Cohort Studies; Cornea; Corneal Diseases; European Continental Ancestry Group; Gene Expression; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Intracellular Signaling Peptides and Proteins; Odds Ratio; Polymorphism, Single Nucleotide; Receptor, Platelet-Derived Growth Factor alpha; Software

A Giant Ovarian Cyst in an Adolescent. - Corrias, Francesca; Pederiva, Federica; Cozzi, Giorgio; Ammar, Lydie; Cattaruzzi, Elisabetta; Lembo, Maria Antonietta; Barbi, Egidio (J Pediatr, 2018)
Keywords: Child; Cystadenoma, Serous; Female; Humans; Ovarian Neoplasms

Girl With Chest Pain. - Scarpa, Maria-Grazia; Rabach, Ingrid; Canuto, Arianna; Sanabor, Daniela; Barbi, Egidio; Schleef, Jurgen (Ann Emerg Med, 2018)

A Girl with Delayed Puberty and Bumpy Lips. - Andrade, Stefanny; Sirchia, Fabio; Faleschini, Elena; Barbi, Egidio (J Pediatr, 2018)
Keywords: Adolescent; Exons; Female; Genes, Dominant; Humans; Lip; Multiple Endocrine Neoplasia Type 2b; Neoplasm Metastasis; Puberty, Delayed; Thyroid Neoplasms; Thyroidectomy; Tongue

Global, regional, and national age-sex-specific mortality and life expectancy, 1950-2017: a systematic analysis for the Global Burden of Disease Study 2017. (Lancet, 2018)
BACKGROUND: Assessments of age-specific mortality and life expectancy have been done by the UN Population Division, Department of Economics and Social Affairs (UNPOP), the United States Census Bureau, WHO, and as part of previous iterations of the Global Burden of Diseases, Injuries, and Risk Factors Study (GBD). Previous iterations of the GBD used population estimates from UNPOP, which were not derived in a way that was internally consistent with the estimates of the numbers of deaths in the GBD. The present iteration of the GBD, GBD 2017, improves on previous assessments and provides timely estimates of the mortality experience of populations globally. METHODS: The GBD uses all available data to produce estimates of mortality rates between 1950 and 2017 for 23 age groups, both sexes, and 918 locations, including 195 countries and territories and subnational locations for 16 countries. Data used include vital registration systems, sample registration systems, household surveys (complete birth histories, summary birth histories, sibling histories), censuses (summary birth histories, household deaths), and Demographic Surveillance Sites. In total, this analysis used 8259 data sources. Estimates of the probability of death between birth and the age of 5 years and between ages 15 and 60 years are generated and then input into a model life table system to produce complete life tables for all locations and years. Fatal discontinuities and mortality due to HIV/AIDS are analysed separately and then incorporated into the estimation. We analyse the relationship between age-specific mortality and development status using the Socio-demographic Index, a composite measure based on fertility under the age of 25 years, education, and income. There are four main methodological improvements in GBD 2017 compared with GBD 2016: 622 additional data sources have been incorporated; new estimates of population, generated by the GBD study, are used; statistical methods used in different components of the analysis have been further standardised and improved; and the analysis has been extended backwards in time by two decades to start in 1950. FINDINGS: Globally, 18·7% (95% uncertainty interval 18·4-19·0) of deaths were registered in 1950 and that proportion has been steadily increasing since, with 58·8% (58·2-59·3) of all deaths being registered in 2015. At the global level, between 1950 and 2017, life expectancy increased from 48·1 years (46·5-49·6) to 70·5 years (70·1-70·8) for men and from 52·9 years (51·7-54·0) to 75·6 years (75·3-75·9) for women. Despite this overall progress, there remains substantial variation in life expectancy at birth in 2017, which ranges from 49·1 years (46·5-51·7) for men in the Central African Republic to 87·6 years (86·9-88·1) among women in Singapore. The greatest progress across age groups was for children younger than 5 years; under-5 mortality dropped from 216·0 deaths (196·3-238·1) per 1000 livebirths in 1950 to 38·9 deaths (35·6-42·83) per 1000 livebirths in 2017, with huge reductions across countries. Nevertheless, there were still 5·4 million (5·2-5·6) deaths among children younger than 5 years in the world in 2017. Progress has been less pronounced and more variable for adults, especially for adult males, who had stagnant or increasing mortality rates in several countries. The gap between male and female life expectancy between 1950 and 2017, while relatively stable at the global level, shows distinctive patterns across super-regions and has consistently been the largest in central Europe, eastern Europe, and central Asia, and smallest in south Asia. Performance was also variable across countries and time in observed mortality rates compared with those expected on the basis of development. INTERPRETATION: This analysis of age-sex-specific mortality shows that there are remarkably complex patterns in population mortality across countries. The findings of this study highlight global successes, such as the large decline in under-5 mortality, which reflects significant local, national, and global commitment and investment over several decades. However, they also bring attention to mortality patterns that are a cause for concern, particularly among adult men and, to a lesser extent, women, whose mortality rates have stagnated in many countries over the time period of this study, and in some cases are increasing. FUNDING: Bill & Melinda Gates Foundation.
Keywords: Adolescent; Adult; Age Distribution; Aged; Aged, 80 and over; Child; Child, Preschool; Female; Global Burden of Disease; Global Health; Humans; Infant; Infant, Newborn; Life Expectancy; Male; Middle Aged; Mortality; Sex Distribution; Socioeconomic Factors; Young Adult

Global, regional, and national age-sex-specific mortality for 282 causes of death in 195 countries and territories, 1980-2017: a systematic analysis for the Global Burden of Disease Study 2017. (Lancet, 2018)
BACKGROUND: Global development goals increasingly rely on country-specific estimates for benchmarking a nation's progress. To meet this need, the Global Burden of Diseases, Injuries, and Risk Factors Study (GBD) 2016 estimated global, regional, national, and, for selected locations, subnational cause-specific mortality beginning in the year 1980. Here we report an update to that study, making use of newly available data and improved methods. GBD 2017 provides a comprehensive assessment of cause-specific mortality for 282 causes in 195 countries and territories from 1980 to 2017. METHODS: The causes of death database is composed of vital registration (VR), verbal autopsy (VA), registry, survey, police, and surveillance data. GBD 2017 added ten VA studies, 127 country-years of VR data, 502 cancer-registry country-years, and an additional surveillance country-year. Expansions of the GBD cause of death hierarchy resulted in 18 additional causes estimated for GBD 2017. Newly available data led to subnational estimates for five additional countries-Ethiopia, Iran, New Zealand, Norway, and Russia. Deaths assigned International Classification of Diseases (ICD) codes for non-specific, implausible, or intermediate causes of death were reassigned to underlying causes by redistribution algorithms that were incorporated into uncertainty estimation. We used statistical modelling tools developed for GBD, including the Cause of Death Ensemble model (CODEm), to generate cause fractions and cause-specific death rates for each location, year, age, and sex. Instead of using UN estimates as in previous versions, GBD 2017 independently estimated population size and fertility rate for all locations. Years of life lost (YLLs) were then calculated as the sum of each death multiplied by the standard life expectancy at each age. All rates reported here are age-standardised. FINDINGS: At the broadest grouping of causes of death (Level 1), non-communicable diseases (NCDs) comprised the greatest fraction of deaths, contributing to 73·4% (95% uncertainty interval [UI] 72·5-74·1) of total deaths in 2017, while communicable, maternal, neonatal, and nutritional (CMNN) causes accounted for 18·6% (17·9-19·6), and injuries 8·0% (7·7-8·2). Total numbers of deaths from NCD causes increased from 2007 to 2017 by 22·7% (21·5-23·9), representing an additional 7·61 million (7·20-8·01) deaths estimated in 2017 versus 2007. The death rate from NCDs decreased globally by 7·9% (7·0-8·8). The number of deaths for CMNN causes decreased by 22·2% (20·0-24·0) and the death rate by 31·8% (30·1-33·3). Total deaths from injuries increased by 2·3% (0·5-4·0) between 2007 and 2017, and the death rate from injuries decreased by 13·7% (12·2-15·1) to 57·9 deaths (55·9-59·2) per 100 000 in 2017. Deaths from substance use disorders also increased, rising from 284 000 deaths (268 000-289 000) globally in 2007 to 352 000 (334 000-363 000) in 2017. Between 2007 and 2017, total deaths from conflict and terrorism increased by 118·0% (88·8-148·6). A greater reduction in total deaths and death rates was observed for some CMNN causes among children younger than 5 years than for older adults, such as a 36·4% (32·2-40·6) reduction in deaths from lower respiratory infections for children younger than 5 years compared with a 33·6% (31·2-36·1) increase in adults older than 70 years. Globally, the number of deaths was greater for men than for women at most ages in 2017, except at ages older than 85 years. Trends in global YLLs reflect an epidemiological transition, with decreases in total YLLs from enteric infections, respiratory infections and tuberculosis, and maternal and neonatal disorders between 1990 and 2017; these were generally greater in magnitude at the lowest levels of the Socio-demographic Index (SDI). At the same time, there were large increases in YLLs from neoplasms and cardiovascular diseases. YLL rates decreased across the five leading Level 2 causes in all SDI quintiles. The leading causes of YLLs in 1990-neonatal disorders, lower respiratory infections, and diarrhoeal diseases-were ranked second, fourth, and fifth, in 2017. Meanwhile, estimated YLLs increased for ischaemic heart disease (ranked first in 2017) and stroke (ranked third), even though YLL rates decreased. Population growth contributed to increased total deaths across the 20 leading Level 2 causes of mortality between 2007 and 2017. Decreases in the cause-specific mortality rate reduced the effect of population growth for all but three causes: substance use disorders, neurological disorders, and skin and subcutaneous diseases. INTERPRETATION: Improvements in global health have been unevenly distributed among populations. Deaths due to injuries, substance use disorders, armed conflict and terrorism, neoplasms, and cardiovascular disease are expanding threats to global health. For causes of death such as lower respiratory and enteric infections, more rapid progress occurred for children than for the oldest adults, and there is continuing disparity in mortality rates by sex across age groups. Reductions in the death rate of some common diseases are themselves slowing or have ceased, primarily for NCDs, and the death rate for selected causes has increased in the past decade. FUNDING: Bill & Melinda Gates Foundation.
Keywords: Adolescent; Adult; Age Distribution; Aged; Aged, 80 and over; Cause of Death; Child; Child, Preschool; Female; Global Burden of Disease; Global Health; Humans; Infant; Infant, Newborn; Life Expectancy; Male; Middle Aged; Sex Distribution; Socioeconomic Factors; Young Adult

Global, regional, and national burden of meningitis, 1990-2016: a systematic analysis for the Global Burden of Disease Study 2016. (Lancet Neurol, 2018)
BACKGROUND: Acute meningitis has a high case-fatality rate and survivors can have severe lifelong disability. We aimed to provide a comprehensive assessment of the levels and trends of global meningitis burden that could help to guide introduction, continuation, and ongoing development of vaccines and treatment programmes. METHODS: The Global Burden of Diseases, Injuries, and Risk Factors (GBD) 2016 study estimated meningitis burden due to one of four types of cause: pneumococcal, meningococcal, Haemophilus influenzae type b, and a residual category of other causes. Cause-specific mortality estimates were generated via cause of death ensemble modelling of vital registration and verbal autopsy data that were subject to standardised data processing algorithms. Deaths were multiplied by the GBD standard life expectancy at age of death to estimate years of life lost, the mortality component of disability-adjusted life-years (DALYs). A systematic analysis of relevant publications and hospital and claims data was used to estimate meningitis incidence via a Bayesian meta-regression tool. Meningitis deaths and cases were split between causes with meta-regressions of aetiological proportions of mortality and incidence, respectively. Probabilities of long-term impairment by cause of meningitis were applied to survivors and used to estimate years of life lived with disability (YLDs). We assessed the relationship between burden metrics and Socio-demographic Index (SDI), a composite measure of development based on fertility, income, and education. FINDINGS: Global meningitis deaths decreased by 21·0% from 1990 to 2016, from 403 012 (95% uncertainty interval [UI] 319 426-458 514) to 318 400 (265 218-408 705). Incident cases globally increased from 2·50 million (95% UI 2·19-2·91) in 1990 to 2·82 million (2·46-3·31) in 2016. Meningitis mortality and incidence were closely related to SDI. The highest mortality rates and incidence rates were found in the peri-Sahelian countries that comprise the African meningitis belt, with six of the ten countries with the largest number of cases and deaths being located within this region. Haemophilus influenzae type b was the most common cause of incident meningitis in 1990, at 780 070 cases (95% UI 613 585-978 219) globally, but decreased the most (-49·1%) to become the least common cause in 2016, with 397 297 cases (291 076-533 662). Meningococcus was the leading cause of meningitis mortality in 1990 (192 833 deaths [95% UI 153 358-221 503] globally), whereas other meningitis was the leading cause for both deaths (136 423 [112 682-178 022]) and incident cases (1·25 million [1·06-1·49]) in 2016. Pneumococcus caused the largest number of YLDs (634 458 [444 787-839 749]) in 2016, owing to its more severe long-term effects on survivors. Globally in 2016, 1·48 million (1·04-1·96) YLDs were due to meningitis compared with 21·87 million (18·20-28·28) DALYs, indicating that the contribution of mortality to meningitis burden is far greater than the contribution of disabling outcomes. INTERPRETATION: Meningitis burden remains high and progress lags substantially behind that of other vaccine-preventable diseases. Particular attention should be given to developing vaccines with broader coverage against the causes of meningitis, making these vaccines affordable in the most affected countries, improving vaccine uptake, improving access to low-cost diagnostics and therapeutics, and improving support for disabled survivors. Substantial uncertainty remains around pathogenic causes and risk factors for meningitis. Ongoing, active cause-specific surveillance of meningitis is crucial to continue and to improve monitoring of meningitis burdens and trends throughout the world. FUNDING: Bill & Melinda Gates Foundation.

Global, regional, and national comparative risk assessment of 84 behavioural, environmental and occupational, and metabolic risks or clusters of risks for 195 countries and territories, 1990-2017: a systematic analysis for the Global Burden of Disease Stu (Lancet, 2018)
BACKGROUND: The Global Burden of Diseases, Injuries, and Risk Factors Study (GBD) 2017 comparative risk assessment (CRA) is a comprehensive approach to risk factor quantification that offers a useful tool for synthesising evidence on risks and risk-outcome associations. With each annual GBD study, we update the GBD CRA to incorporate improved methods, new risks and risk-outcome pairs, and new data on risk exposure levels and risk-outcome associations. METHODS: We used the CRA framework developed for previous iterations of GBD to estimate levels and trends in exposure, attributable deaths, and attributable disability-adjusted life-years (DALYs), by age group, sex, year, and location for 84 behavioural, environmental and occupational, and metabolic risks or groups of risks from 1990 to 2017. This study included 476 risk-outcome pairs that met the GBD study criteria for convincing or probable evidence of causation. We extracted relative risk and exposure estimates from 46 749 randomised controlled trials, cohort studies, household surveys, census data, satellite data, and other sources. We used statistical models to pool data, adjust for bias, and incorporate covariates. Using the counterfactual scenario of theoretical minimum risk exposure level (TMREL), we estimated the portion of deaths and DALYs that could be attributed to a given risk. We explored the relationship between development and risk exposure by modelling the relationship between the Socio-demographic Index (SDI) and risk-weighted exposure prevalence and estimated expected levels of exposure and risk-attributable burden by SDI. Finally, we explored temporal changes in risk-attributable DALYs by decomposing those changes into six main component drivers of change as follows: (1) population growth; (2) changes in population age structures; (3) changes in exposure to environmental and occupational risks; (4) changes in exposure to behavioural risks; (5) changes in exposure to metabolic risks; and (6) changes due to all other factors, approximated as the risk-deleted death and DALY rates, where the risk-deleted rate is the rate that would be observed had we reduced the exposure levels to the TMREL for all risk factors included in GBD 2017. FINDINGS: In 2017, 34·1 million (95% uncertainty interval [UI] 33·3-35·0) deaths and 1·21 billion (1·14-1·28) DALYs were attributable to GBD risk factors. Globally, 61·0% (59·6-62·4) of deaths and 48·3% (46·3-50·2) of DALYs were attributed to the GBD 2017 risk factors. When ranked by risk-attributable DALYs, high systolic blood pressure (SBP) was the leading risk factor, accounting for 10·4 million (9·39-11·5) deaths and 218 million (198-237) DALYs, followed by smoking (7·10 million [6·83-7·37] deaths and 182 million [173-193] DALYs), high fasting plasma glucose (6·53 million [5·23-8·23] deaths and 171 million [144-201] DALYs), high body-mass index (BMI; 4·72 million [2·99-6·70] deaths and 148 million [98·6-202] DALYs), and short gestation for birthweight (1·43 million [1·36-1·51] deaths and 139 million [131-147] DALYs). In total, risk-attributable DALYs declined by 4·9% (3·3-6·5) between 2007 and 2017. In the absence of demographic changes (ie, population growth and ageing), changes in risk exposure and risk-deleted DALYs would have led to a 23·5% decline in DALYs during that period. Conversely, in the absence of changes in risk exposure and risk-deleted DALYs, demographic changes would have led to an 18·6% increase in DALYs during that period. The ratios of observed risk exposure levels to exposure levels expected based on SDI (O/E ratios) increased globally for unsafe drinking water and household air pollution between 1990 and 2017. This result suggests that development is occurring more rapidly than are changes in the underlying risk structure in a population. Conversely, nearly universal declines in O/E ratios for smoking and alcohol use indicate that, for a given SDI, exposure to these risks is declining. In 2017, the leading Level 4 risk factor for age-standardised DALY rates was high SBP in four super-regions: central Europe, eastern Europe, and central Asia; north Africa and Middle East; south Asia; and southeast Asia, east Asia, and Oceania. The leading risk factor in the high-income super-region was smoking, in Latin America and Caribbean was high BMI, and in sub-Saharan Africa was unsafe sex. O/E ratios for unsafe sex in sub-Saharan Africa were notably high, and those for alcohol use in north Africa and the Middle East were notably low. INTERPRETATION: By quantifying levels and trends in exposures to risk factors and the resulting disease burden, this assessment offers insight into where past policy and programme efforts might have been successful and highlights current priorities for public health action. Decreases in behavioural, environmental, and occupational risks have largely offset the effects of population growth and ageing, in relation to trends in absolute burden. Conversely, the combination of increasing metabolic risks and population ageing will probably continue to drive the increasing trends in non-communicable diseases at the global level, which presents both a public health challenge and opportunity. We see considerable spatiotemporal heterogeneity in levels of risk exposure and risk-attributable burden. Although levels of development underlie some of this heterogeneity, O/E ratios show risks for which countries are overperforming or underperforming relative to their level of development. As such, these ratios provide a benchmarking tool to help to focus local decision making. Our findings reinforce the importance of both risk exposure monitoring and epidemiological research to assess causal connections between risks and health outcomes, and they highlight the usefulness of the GBD study in synthesising data to draw comprehensive and robust conclusions that help to inform good policy and strategic health planning. FUNDING: Bill & Melinda Gates Foundation.
Keywords: Adolescent; Adult; Age Distribution; Aged; Aged, 80 and over; Child; Child, Preschool; Disabled Persons; Environmental Exposure; Female; Global Burden of Disease; Global Health; Health Risk Behaviors; Humans; Infant; Infant, Newborn; Life Expectancy; Male; Metabolic Diseases; Middle Aged; Occupational Diseases; Occupational Exposure; Quality-Adjusted Life Years; Risk Assessment; Sex Distribution; Socioeconomic Factors; Young Adult

Global, regional, and national disability-adjusted life-years (DALYs) for 359 diseases and injuries and healthy life expectancy (HALE) for 195 countries and territories, 1990-2017: a systematic analysis for the Global Burden of Disease Study 2017. (Lancet, 2018)
BACKGROUND: How long one lives, how many years of life are spent in good and poor health, and how the population's state of health and leading causes of disability change over time all have implications for policy, planning, and provision of services. We comparatively assessed the patterns and trends of healthy life expectancy (HALE), which quantifies the number of years of life expected to be lived in good health, and the complementary measure of disability-adjusted life-years (DALYs), a composite measure of disease burden capturing both premature mortality and prevalence and severity of ill health, for 359 diseases and injuries for 195 countries and territories over the past 28 years. METHODS: We used data for age-specific mortality rates, years of life lost (YLLs) due to premature mortality, and years lived with disability (YLDs) from the Global Burden of Diseases, Injuries, and Risk Factors Study (GBD) 2017 to calculate HALE and DALYs from 1990 to 2017. We calculated HALE using age-specific mortality rates and YLDs per capita for each location, age, sex, and year. We calculated DALYs for 359 causes as the sum of YLLs and YLDs. We assessed how observed HALE and DALYs differed by country and sex from expected trends based on Socio-demographic Index (SDI). We also analysed HALE by decomposing years of life gained into years spent in good health and in poor health, between 1990 and 2017, and extra years lived by females compared with males. FINDINGS: Globally, from 1990 to 2017, life expectancy at birth increased by 7·4 years (95% uncertainty interval 7·1-7·8), from 65·6 years (65·3-65·8) in 1990 to 73·0 years (72·7-73·3) in 2017. The increase in years of life varied from 5·1 years (5·0-5·3) in high SDI countries to 12·0 years (11·3-12·8) in low SDI countries. Of the additional years of life expected at birth, 26·3% (20·1-33·1) were expected to be spent in poor health in high SDI countries compared with 11·7% (8·8-15·1) in low-middle SDI countries. HALE at birth increased by 6·3 years (5·9-6·7), from 57·0 years (54·6-59·1) in 1990 to 63·3 years (60·5-65·7) in 2017. The increase varied from 3·8 years (3·4-4·1) in high SDI countries to 10·5 years (9·8-11·2) in low SDI countries. Even larger variations in HALE than these were observed between countries, ranging from 1·0 year (0·4-1·7) in Saint Vincent and the Grenadines (62·4 years [59·9-64·7] in 1990 to 63·5 years [60·9-65·8] in 2017) to 23·7 years (21·9-25·6) in Eritrea (30·7 years [28·9-32·2] in 1990 to 54·4 years [51·5-57·1] in 2017). In most countries, the increase in HALE was smaller than the increase in overall life expectancy, indicating more years lived in poor health. In 180 of 195 countries and territories, females were expected to live longer than males in 2017, with extra years lived varying from 1·4 years (0·6-2·3) in Algeria to 11·9 years (10·9-12·9) in Ukraine. Of the extra years gained, the proportion spent in poor health varied largely across countries, with less than 20% of additional years spent in poor health in Bosnia and Herzegovina, Burundi, and Slovakia, whereas in Bahrain all the extra years were spent in poor health. In 2017, the highest estimate of HALE at birth was in Singapore for both females (75·8 years [72·4-78·7]) and males (72·6 years [69·8-75·0]) and the lowest estimates were in Central African Republic (47·0 years [43·7-50·2] for females and 42·8 years [40·1-45·6] for males). Globally, in 2017, the five leading causes of DALYs were neonatal disorders, ischaemic heart disease, stroke, lower respiratory infections, and chronic obstructive pulmonary disease. Between 1990 and 2017, age-standardised DALY rates decreased by 41·3% (38·8-43·5) for communicable diseases and by 49·8% (47·9-51·6) for neonatal disorders. For non-communicable diseases, global DALYs increased by 40·1% (36·8-43·0), although age-standardised DALY rates decreased by 18·1% (16·0-20·2). INTERPRETATION: With increasing life expectancy in most countries, the question of whether the additional years of life gained are spent in good health or poor health has been increasingly relevant because of the potential policy implications, such as health-care provisions and extending retirement ages. In some locations, a large proportion of those additional years are spent in poor health. Large inequalities in HALE and disease burden exist across countries in different SDI quintiles and between sexes. The burden of disabling conditions has serious implications for health system planning and health-related expenditures. Despite the progress made in reducing the burden of communicable diseases and neonatal disorders in low SDI countries, the speed of this progress could be increased by scaling up proven interventions. The global trends among non-communicable diseases indicate that more effort is needed to maximise HALE, such as risk prevention and attention to upstream determinants of health. FUNDING: Bill & Melinda Gates Foundation.
Keywords: Aged; Communicable Diseases; Disabled Persons; Female; Global Burden of Disease; Health Status; Healthy Lifestyle; Humans; Life Expectancy; Male; Mortality; Mortality, Premature; Prevalence; Quality-Adjusted Life Years; Risk Factors; Socioeconomic Factors; Wounds and Injuries

Global, regional, and national incidence, prevalence, and years lived with disability for 354 diseases and injuries for 195 countries and territories, 1990-2017: a systematic analysis for the Global Burden of Disease Study 2017. (Lancet, 2018)
BACKGROUND: The Global Burden of Diseases, Injuries, and Risk Factors Study 2017 (GBD 2017) includes a comprehensive assessment of incidence, prevalence, and years lived with disability (YLDs) for 354 causes in 195 countries and territories from 1990 to 2017. Previous GBD studies have shown how the decline of mortality rates from 1990 to 2016 has led to an increase in life expectancy, an ageing global population, and an expansion of the non-fatal burden of disease and injury. These studies have also shown how a substantial portion of the world's population experiences non-fatal health loss with considerable heterogeneity among different causes, locations, ages, and sexes. Ongoing objectives of the GBD study include increasing the level of estimation detail, improving analytical strategies, and increasing the amount of high-quality data. METHODS: We estimated incidence and prevalence for 354 diseases and injuries and 3484 sequelae. We used an updated and extensive body of literature studies, survey data, surveillance data, inpatient admission records, outpatient visit records, and health insurance claims, and additionally used results from cause of death models to inform estimates using a total of 68 781 data sources. Newly available clinical data from India, Iran, Japan, Jordan, Nepal, China, Brazil, Norway, and Italy were incorporated, as well as updated claims data from the USA and new claims data from Taiwan (province of China) and Singapore. We used DisMod-MR 2.1, a Bayesian meta-regression tool, as the main method of estimation, ensuring consistency between rates of incidence, prevalence, remission, and cause of death for each condition. YLDs were estimated as the product of a prevalence estimate and a disability weight for health states of each mutually exclusive sequela, adjusted for comorbidity. We updated the Socio-demographic Index (SDI), a summary development indicator of income per capita, years of schooling, and total fertility rate. Additionally, we calculated differences between male and female YLDs to identify divergent trends across sexes. GBD 2017 complies with the Guidelines for Accurate and Transparent Health Estimates Reporting. FINDINGS: Globally, for females, the causes with the greatest age-standardised prevalence were oral disorders, headache disorders, and haemoglobinopathies and haemolytic anaemias in both 1990 and 2017. For males, the causes with the greatest age-standardised prevalence were oral disorders, headache disorders, and tuberculosis including latent tuberculosis infection in both 1990 and 2017. In terms of YLDs, low back pain, headache disorders, and dietary iron deficiency were the leading Level 3 causes of YLD counts in 1990, whereas low back pain, headache disorders, and depressive disorders were the leading causes in 2017 for both sexes combined. All-cause age-standardised YLD rates decreased by 3·9% (95% uncertainty interval [UI] 3·1-4·6) from 1990 to 2017; however, the all-age YLD rate increased by 7·2% (6·0-8·4) while the total sum of global YLDs increased from 562 million (421-723) to 853 million (642-1100). The increases for males and females were similar, with increases in all-age YLD rates of 7·9% (6·6-9·2) for males and 6·5% (5·4-7·7) for females. We found significant differences between males and females in terms of age-standardised prevalence estimates for multiple causes. The causes with the greatest relative differences between sexes in 2017 included substance use disorders (3018 cases [95% UI 2782-3252] per 100 000 in males vs s1400 [1279-1524] per 100 000 in females), transport injuries (3322 [3082-3583] vs 2336 [2154-2535]), and self-harm and interpersonal violence (3265 [2943-3630] vs 5643 [5057-6302]). INTERPRETATION: Global all-cause age-standardised YLD rates have improved only slightly over a period spanning nearly three decades. However, the magnitude of the non-fatal disease burden has expanded globally, with increasing numbers of people who have a wide spectrum of conditions. A subset of conditions has remained globally pervasive since 1990, whereas other conditions have displayed more dynamic trends, with different ages, sexes, and geographies across the globe experiencing varying burdens and trends of health loss. This study emphasises how global improvements in premature mortality for select conditions have led to older populations with complex and potentially expensive diseases, yet also highlights global achievements in certain domains of disease and injury. FUNDING: Bill & Melinda Gates Foundation.
Keywords: Adolescent; Adult; Age Distribution; Aged; Aged, 80 and over; Child; Child, Preschool; Disabled Persons; Female; Global Burden of Disease; Global Health; Humans; Incidence; Infant; Infant, Newborn; Life Expectancy; Male; Middle Aged; Morbidity; Prevalence; Sex Distribution; Socioeconomic Factors; Wounds and Injuries; Young Adult

Gut microbiota characterisation in obese patients before and after bariatric surgery. - Campisciano, G; Palmisano, S; Cason, C; Giuricin, M; Silvestri, M; Guerra, M; Macor, D; De Manzini, N; Crocé, L S; Comar, M (Benef Microbes, 2018)
Intestinal microbiota analysis of obese patients after bariatric surgery showed that Proteobacteria decreased after laparoscopic sleeve gastrectomy (SG), while it increased after laparoscopic gastric bypass (LGB). Comparing to normal weight (NW) patients, obese patients that were selected for SG showed an almost equal amount of Firmicutes and Bacteroidetes and the ratio was not affected by the surgery. Obese patients before LGB showed a predominance of Bacteroidetes, whose amount regained a relative abundance similar to NW patients after surgery. Obese patients before LGB showed the predominance of Bacteroides, which decreased after surgery in favour of Prevotella, a bacterium associated with a healthy diet. The bacteria detected at the highest percentages belonged to biofilm forming species. In conclusion, in this study, we found that the characterization of the gut microbial communities and the modality of mucosal colonisation have a central role as markers for the clinical management of obesity and promote the maintenance of good health and the weight loss.
Keywords: Adult; Bariatric Surgery; Gastrointestinal Microbiome; Humans; Laparoscopy; Microbiota; Middle Aged; Obesity; Young Adult

Genetic structure in the Sherpa and neighboring Nepalese populations. - Cole, Amy M; Cox, Sean; Jeong, Choongwon; Petousi, Nayia; Aryal, Dhana R; Droma, Yunden; Hanaoka, Masayuki; Ota, Masao; Kobayashi, Nobumitsu; Gasparini, Paolo; Montgomery, Hugh; Robbins, Peter; et al. (BMC Genomics, 2017)
BACKGROUND: We set out to describe the fine-scale population structure across the Eastern region of Nepal. To date there is relatively little known about the genetic structure of the Sherpa residing in Nepal and their genetic relationship with the Nepalese. We assembled dense genotype data from a total of 1245 individuals representing Nepal and a variety of different populations resident across the greater Himalayan region including Tibet, China, India, Pakistan, Kazakhstan, Uzbekistan, Tajikistan and Kirghizstan. We performed analysis of principal components, admixture and homozygosity. RESULTS: We identified clear substructure across populations resident in the Himalayan arc, with genetic structure broadly mirroring geographical features of the region. Ethnic subgroups within Nepal show distinct genetic structure, on both admixture and principal component analysis. We detected differential proportions of ancestry from northern Himalayan populations across Nepalese subgroups, with the Nepalese Rai, Magar and Tamang carrying the greatest proportions of Tibetan ancestry. CONCLUSIONS: We show that populations dwelling on the Himalayan plateau have had a clear impact on the Northern Indian gene pool. We illustrate how the Sherpa are a remarkably isolated population, with little gene flow from surrounding Nepalese populations.
Keywords: Asian Continental Ancestry Group; Chromosomes, Human, Y; DNA; DNA, Mitochondrial; Ethnic Groups; Gene Flow; Genotype; Humans; Leukocytes; Likelihood Functions; Nepal; Principal Component Analysis

Genome-wide association analysis identifies novel blood pressure loci and offers biological insights into cardiovascular risk. - Warren, Helen R; Evangelou, Evangelos; Cabrera, Claudia P; Gao, He; Ren, Meixia; Mifsud, Borbala; Ntalla, Ioanna; Surendran, Praveen; Liu, Chunyu; Cook, James P; Kraja, Aldi T; Drenos, Fotios; et al. (Nat Genet, 2017)
Elevated blood pressure is the leading heritable risk factor for cardiovascular disease worldwide. We report genetic association of blood pressure (systolic, diastolic, pulse pressure) among UK Biobank participants of European ancestry with independent replication in other cohorts, and robust validation of 107 independent loci. We also identify new independent variants at 11 previously reported blood pressure loci. In combination with results from a range of in silico functional analyses and wet bench experiments, our findings highlight new biological pathways for blood pressure regulation enriched for genes expressed in vascular tissues and identify potential therapeutic targets for hypertension. Results from genetic risk score models raise the possibility of a precision medicine approach through early lifestyle intervention to offset the impact of blood pressure-raising genetic variants on future cardiovascular disease risk.
Keywords: Adult; Blood Pressure; Cardiovascular Diseases; European Continental Ancestry Group; Female; Genetic Loci; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Hypertension; Male; Middle Aged; Polymorphism, Single Nucleotide; Risk Factors

Genomic analyses identify hundreds of variants associated with age at menarche and support a role for puberty timing in cancer risk. - Day, Felix R; Thompson, Deborah J; Helgason, Hannes; Chasman, Daniel I; Finucane, Hilary; Sulem, Patrick; Ruth, Katherine S; Whalen, Sean; Sarkar, Abhishek K; Albrecht, Eva; Altmaier, Elisabeth; Amini, Marzyeh; et al. (Nat Genet, 2017)
The timing of puberty is a highly polygenic childhood trait that is epidemiologically associated with various adult diseases. Using 1000 Genomes Project-imputed genotype data in up to ∼370,000 women, we identify 389 independent signals (P < 5 × 10) for age at menarche, a milestone in female pubertal development. In Icelandic data, these signals explain ∼7.4% of the population variance in age at menarche, corresponding to ∼25% of the estimated heritability. We implicate ∼250 genes via coding variation or associated expression, demonstrating significant enrichment in neural tissues. Rare variants near the imprinted genes MKRN3 and DLK1 were identified, exhibiting large effects when paternally inherited. Mendelian randomization analyses suggest causal inverse associations, independent of body mass index (BMI), between puberty timing and risks for breast and endometrial cancers in women and prostate cancer in men. In aggregate, our findings highlight the complexity of the genetic regulation of puberty timing and support causal links with cancer susceptibility.
Keywords: Adolescent; Age Factors; Body Mass Index; Databases, Genetic; Female; Genetic Predisposition to Disease; Genome-Wide Association Study; Genomic Imprinting; Humans; Intercellular Signaling Peptides and Proteins; Male; Membrane Proteins; Menarche; Neoplasms; Polymorphism, Single Nucleotide; Puberty; Quantitative Trait Loci; Ribonucleoproteins; Risk Factors

Gray platelet syndrome: Novel mutations of the NBEAL2 gene. - Bottega, Roberta; Nicchia, Elena; Alfano, Caterina; Glembotsky, Ana C; Pastore, Annalisa; Bertaggia-Calderara, Debora; Bisig, Bettina; Duchosal, Michel A; Arbesú, Guillermo; Alberio, Lorenzo; Heller, Paula G; Savoia, Anna (Am J Hematol, 2017)
Keywords: Adult; Alleles; Blood Proteins; Child; Female; Gene Expression; Gene Frequency; Genotype; Gray Platelet Syndrome; Humans; Male; Mutation; Phenotype; Platelet Aggregation; Platelet Count; Platelet Membrane Glycoproteins

Guidelines of the Italian Society of Videosurgery in Infancy for the minimally invasive treatment of the esophageal atresia. - Chiarenza, Salvatore Fabio; Conighi, Maria Luisa; Conforti, Andrea; Esposito, Ciro; Escolino, Maria; Beretta, Fabio; Cheli, Maurizio; Di Benedetto, Vincenzo; Scuderi, Maria Grazia; Casadio, Giovanni; Marzaro, Maurizio; Fascetti, Leon Francesco; et al. (Pediatr Med Chir, 2017)
Not available.
Keywords: Esophageal Atresia; Humans; Infant; Minimally Invasive Surgical Procedures; Video-Assisted Surgery

Guidelines of the Italian Society of Videosurgery in Infancy for the minimally invasive treatment of the ureteropelvic-junction obstruction. - Chiarenza, Salvatore Fabio; Bleve, Cosimo; Esposito, Ciro; Escolino, Maria; Beretta, Fabio; Cheli, Maurizio; Di Benedetto, Vincenzo; Scuderi, Maria Grazia; Casadio, Giovanni; Marzaro, Maurizio; Fascetti, Leon Francesco; Bagolan, Pietro; et al. (Pediatr Med Chir, 2017)
Not available.
Keywords: Humans; Infant; Kidney Pelvis; Minimally Invasive Surgical Procedures; Ureteral Obstruction; Video-Assisted Surgery

Genetic associations at 53 loci highlight cell types and biological pathways relevant for kidney function. - Pattaro, Cristian; Teumer, Alexander; Gorski, Mathias; Chu, Audrey Y; Li, Man; Mijatovic, Vladan; Garnaas, Maija; Tin, Adrienne; Sorice, Rossella; Li, Yong; Taliun, Daniel; Olden, Matthias; et al. (Nat Commun, 2016)
Reduced glomerular filtration rate defines chronic kidney disease and is associated with cardiovascular and all-cause mortality. We conducted a meta-analysis of genome-wide association studies for estimated glomerular filtration rate (eGFR), combining data across 133,413 individuals with replication in up to 42,166 individuals. We identify 24 new and confirm 29 previously identified loci. Of these 53 loci, 19 associate with eGFR among individuals with diabetes. Using bioinformatics, we show that identified genes at eGFR loci are enriched for expression in kidney tissues and in pathways relevant for kidney development and transmembrane transporter activity, kidney structure, and regulation of glucose metabolism. Chromatin state mapping and DNase I hypersensitivity analyses across adult tissues demonstrate preferential mapping of associated variants to regulatory regions in kidney but not extra-renal tissues. These findings suggest that genetic determinants of eGFR are mediated largely through direct effects within the kidney and highlight important cell types and biological pathways.
Keywords: Gene Expression Regulation; Genetic Predisposition to Disease; Genome-Wide Association Study; Genotype; Humans; Renal Insufficiency, Chronic

Genome-wide association study identifies 74 loci associated with educational attainment. - Okbay, Aysu; Beauchamp, Jonathan P; Fontana, Mark Alan; Lee, James J; Pers, Tune H; Rietveld, Cornelius A; Turley, Patrick; Chen, Guo-Bo; Emilsson, Valur; Meddens, S Fleur W; Oskarsson, Sven; Pickrell, Joseph K; et al. (Nature, 2016)
Educational attainment is strongly influenced by social and other environmental factors, but genetic factors are estimated to account for at least 20% of the variation across individuals. Here we report the results of a genome-wide association study (GWAS) for educational attainment that extends our earlier discovery sample of 101,069 individuals to 293,723 individuals, and a replication study in an independent sample of 111,349 individuals from the UK Biobank. We identify 74 genome-wide significant loci associated with the number of years of schooling completed. Single-nucleotide polymorphisms associated with educational attainment are disproportionately found in genomic regions regulating gene expression in the fetal brain. Candidate genes are preferentially expressed in neural tissue, especially during the prenatal period, and enriched for biological pathways involved in neural development. Our findings demonstrate that, even for a behavioural phenotype that is mostly environmentally determined, a well-powered GWAS identifies replicable associated genetic variants that suggest biologically relevant pathways. Because educational attainment is measured in large numbers of individuals, it will continue to be useful as a proxy phenotype in efforts to characterize the genetic influences of related phenotypes, including cognition and neuropsychiatric diseases.
Keywords: Alzheimer Disease; Bipolar Disorder; Brain; Cognition; Computational Biology; Educational Status; Fetus; Gene Expression Regulation; Gene-Environment Interaction; Genome-Wide Association Study; Great Britain; Humans; Molecular Sequence Annotation; Polymorphism, Single Nucleotide; Schizophrenia

A Genome-Wide Association Study in isolated populations reveals new genes associated to common food likings. - Pirastu, Nicola; Kooyman, Maarten; Traglia, Michela; Robino, Antonietta; Willems, Sara M; Pistis, Giorgio; Amin, Najaf; Sala, Cinzia; Karssen, Lennart C; van Duijn, Cornelia; Toniolo, Daniela; Gasparini, Paolo (Rev Endocr Metab Disord, 2016)
Food preferences are the first factor driving food choice and thus nutrition. They involve numerous different senses such as taste and olfaction as well as various other factors such as personal experiences and hedonistic aspects. Although it is clear that several of these have a genetic basis, up to now studies have focused mostly on the effects of polymorphisms of taste receptor genes. Therefore, we have carried out one of the first large scale (4611 individuals) GWAS on food likings assessed for 20 specific food likings belonging to 4 different categories (vegetables, fatty, dairy and bitter). A two-step meta-analysis using three different isolated populations from Italy for the discovery step and two populations from The Netherlands and Central Asia for replication, revealed 15 independent genome-wide significant loci (p < 5 × 10(-8)) for 12 different foods. None of the identified genes coded for either taste or olfactory receptors suggesting that genetics impacts in determining food likings in a much broader way than simple differences in taste perception. These results represent a further step in uncovering the genes that underlie liking of common foods that in the end will greatly help understanding the genetics of human nutrition in general.

Geranylgeraniol and Neurological Impairment: Involvement of Apoptosis and Mitochondrial Morphology. - Marcuzzi, Annalisa; Piscianz, Elisa; Zweyer, Marina; Bortul, Roberta; Loganes, Claudia; Girardelli, Martina; Baj, Gabriele; Monasta, Lorenzo; Celeghini, Claudio (Int J Mol Sci, 2016)
Deregulation of the cholesterol pathway is an anomaly observed in human diseases, many of which have in common neurological involvement and unknown pathogenesis. In this study we have used Mevalonate Kinase Deficiency (MKD) as a disease-model in order to investigate the link between the deregulation of the mevalonate pathway and the consequent neurodegeneration. The blocking of the mevalonate pathway in a neuronal cell line (Daoy), using statins or mevalonate, induced an increase in the expression of the inflammasome gene (NLRP3) and programmed cell death related to mitochondrial dysfunction. The morphology of the mitochondria changed, clearly showing the damage induced by oxidative stress and the decreased membrane potential associated with the alterations of the mitochondrial function. The co-administration of geranylgeraniol (GGOH) reduced the inflammatory marker and the damage of the mitochondria, maintaining its shape and components. Our data allow us to speculate about the mechanism by which isoprenoids are able to rescue the inflammatory marker in neuronal cells, independently from the block of the mevalonate pathway, and about the fact that cell death is mitochondria-related.

Giant Cerebellar Lesion in a Patient With Purulent Ear Drainage. - Mandalà, Marco; Muzzi, Enrico; Trabalzini, Franco (JAMA Otolaryngol Head Neck Surg, 2016)

Global diversity in the TAS2R38 bitter taste receptor: revisiting a classic evolutionary PROPosal. - Risso, Davide S; Mezzavilla, Massimo; Pagani, Luca; Robino, Antonietta; Morini, Gabriella; Tofanelli, Sergio; Carrai, Maura; Campa, Daniele; Barale, Roberto; Caradonna, Fabio; Gasparini, Paolo; Luiselli, Donata; et al. (Sci Rep, 2016)
The ability to taste phenylthiocarbamide (PTC) and 6-n-propylthiouracil (PROP) is a polymorphic trait mediated by the TAS2R38 bitter taste receptor gene. It has long been hypothesized that global genetic diversity at this locus evolved under pervasive pressures from balancing natural selection. However, recent high-resolution population genetic studies of TAS2Rs suggest that demographic events have played a critical role in the evolution of these genes. We here utilized the largest TAS2R38 database yet analyzed, consisting of 5,589 individuals from 105 populations, to examine natural selection, haplotype frequencies and linkage disequilibrium to estimate the effects of both selection and demography on contemporary patterns of variation at this locus. We found signs of an ancient balancing selection acting on this gene but no post Out-Of-Africa departures from neutrality, implying that the current observed patterns of variation can be predominantly explained by demographic, rather than selective events. In addition, we found signatures of ancient selective forces acting on different African TAS2R38 haplotypes. Collectively our results provide evidence for a relaxation of recent selective forces acting on this gene and a revised hypothesis for the origins of the present-day worldwide distribution of TAS2R38 haplotypes.

The Great Pretender: Pediatric Wandering Spleen: Two Case Reports and Review of the Literature. - Radillo, Lucia; Taddio, Andrea; Ghirardo, Sergio; Bramuzzo, Matteo; Pederiva, Federica; Maschio, Massimo; Barbi, Egidio (Pediatr Emerg Care, 2016)
Wandering spleen is a rare condition, typically not only due to embryological defects of the splenic ligaments, but also secondary to trauma and splenomegaly. The most common presentation is acute abdomen with a mobile abdominal mass or recurrent abdominal pain. However, the spleen may be temporary in its normal position, and patients could be asymptomatic. A familiarity, if present, strengthens the diagnostic suspect.Abdominal ultrasonography and computed tomography are the examination of choice, and the management is surgical.

Genetic analysis of Italian patients with congenital tufting enteropathy. - d'Apolito, Maria; Pisanelli, Daniela; Faletra, Flavio; Giardino, Ida; Gigante, Maddalena; Pettoello-Mantovani, Massimo; Goulet, Olivier; Gasparini, Paolo; Campanozzi, Angelo (World J Pediatr, 2015)
BACKGROUND: Congenital tufting enteropathy (CTE), an inherited autosomal recessive rare disease, is a severe diarrhea of infancy which is clinically characterized by absence of inflammation and presence of intestinal villous atrophy. Mutations in the EpCAM gene were identified to cause CTE. Recent cases of syndromic tufting enteropathy harboring the SPINT2 (19q13.2) mutation were described. METHODS: Four CTE Italian patients were clinically and immunohistochemically characterized. Direct DNA sequencing of EpCAM and SPINT2 genes was performed. RESULTS: All patients were of Italian origin. Three different mutations were detected (p.Asp219Metfs*15, Tyr186Phefs*6 and p.Ile146Asn) in the EpCAM gene; one of them is novel (p.Ile146Asn). Two patients (P1 and P2) showed compound heterozygosity revealing two mutations in separate alleles. A third patient (P3) was heterozygous for only one novel EpCAM missense mutation (p.Ile146Asn). In a syndromic patient (P4), no deleterious EpCAM mutation was found. Additional SPINT2 mutational analysis was performed. P4 showed a homozygous SPINT2 mutation (p.Y163C). No SPINT2 mutation was found in P3. CLDN7 was also evaluated as a candidate gene by mutational screening in P3 but no mutation was identified. CONCLUSIONS: This study presented a molecular characterization of CTE Italian patients, and identified three mutations in the EpCAM gene and one in the SPINT2 gene. One of EpCAM mutations was novel, therefore increasing the mutational spectrum of allelic variants of the EpCAM gene. Molecular analysis of the SPINT2 gene also allowed us to identify a SPINT2 substitution mutation (c.488A>G) recently found to be associated with syndromic CTE subjects.

Genetic determinants for methotrexate response in juvenile idiopathic arthritis. - Pastore, Serena; Stocco, Gabriele; Favretto, Diego; De Iudicibus, Sara; Taddio, Andrea; d'Adamo, Pio; Malusà, Noelia; Addobbati, Riccardo; Decorti, Giuliana; Lepore, Loredana; Ventura, Alessandro (Front Pharmacol, 2015)
Juvenile idiopathic arthritis (JIAs) is the most common chronic rheumatic disease of childhood and is an important cause of disability. The folic acid analog methotrexate is the first choice disease-modifying anti-rheumatic drug in this disease, however, 35-45% of patients fail to respond. Molecular elements, such as variants in genes of pharmacological relevance, influencing response to methotrexate in JIA, would be important to individualize treatment strategies. Several studies have evaluated the effects of candidate genetic variants in the complex pathway of genes involved in methotrexate pharmacodynamics and pharmacokinetics, however, results are still contrasting and no definitive genetic marker of methotrexate response useful for the clinician to tailor therapy of children with JIA has been identified. Recently, genome-wide approaches have been applied, identifying new potential biological processes involved in methotrexate response in JIA such as TGF-beta signaling and calcium channels. If these genomic results are properly validated and integrated with innovative analyses comprising deep sequencing, epigenetics, and pharmacokinetics, they will greatly contribute to personalize therapy with methotrexate in children with JIA.

Genetic evidence for an origin of the Armenians from Bronze Age mixing of multiple populations. - Haber, Marc; Mezzavilla, Massimo; Xue, Yali; Comas, David; Gasparini, Paolo; Zalloua, Pierre; Tyler-Smith, Chris (Eur J Hum Genet, 2015)
The Armenians are a culturally isolated population who historically inhabited a region in the Near East bounded by the Mediterranean and Black seas and the Caucasus, but remain under-represented in genetic studies and have a complex history including a major geographic displacement during World War I. Here, we analyse genome-wide variation in 173 Armenians and compare them with 78 other worldwide populations. We find that Armenians form a distinctive cluster linking the Near East, Europe, and the Caucasus. We show that Armenian diversity can be explained by several mixtures of Eurasian populations that occurred between ~3000 and ~2000 bce, a period characterized by major population migrations after the domestication of the horse, appearance of chariots, and the rise of advanced civilizations in the Near East. However, genetic signals of population mixture cease after ~1200 bce when Bronze Age civilizations in the Eastern Mediterranean world suddenly and violently collapsed. Armenians have since remained isolated and genetic structure within the population developed ~500 years ago when Armenia was divided between the Ottomans and the Safavid Empire in Iran. Finally, we show that Armenians have higher genetic affinity to Neolithic Europeans than other present-day Near Easterners, and that 29% of Armenian ancestry may originate from an ancestral population that is best represented by Neolithic Europeans.European Journal of Human Genetics advance online publication, 21 October 2015; doi:10.1038/ejhg.2015.206.

Genetic profiling of autoinflammatory disorders in patients with periodic fever: a prospective study. - De Pieri, Carlo; Vuch, Josef; De Martino, Eleonora; Bianco, Anna M; Ronfani, Luca; Athanasakis, Emmanouil; Bortot, Barbara; Crovella, Sergio; Taddio, Andrea; Severini, Giovanni M; Tommasini, Alberto (Pediatr Rheumatol Online J, 2015)
BACKGROUND: Periodic fever syndromes (PFS) are an emerging group of autoinflammatory disorders. Clinical overlap exists and multiple genetic analyses may be needed to assist diagnosis. We evaluated the diagnostic value of a 5-gene sequencing panel (5GP) in patients with undiagnosed PFS. METHODS: Simultaneous double strand Sanger sequencing of MEFV, MVK, TNFRSF1A, NLRP3, NLRP12 genes was performed in 42 patients with unexplained PFS. Clinical features were correlated with genetic results. RESULTS: None of 42 patients analyzed displayed a causative genotype. However, single or multiple genetic variants of uncertain significance were detected in 24 subjects. Only in 5 subjects a definite diagnosis was made by taking into account both genetic and clinical data (2 TRAPS syndrome; 2 FMF; 1 FCAS). Statistical analysis showed that patients carrying genetic variants in one or more of the five selected genes displayed a significantly lower response to glucocorticoids compared with subjects who had completely negative genetic results. CONCLUSIONS: The sequencing of multiple genes is of little help in the diagnostics of PFS and can often lead to results of uncertain interpretation, thus the clinically driven sequencing of single genes should remain the recommended approach. However, the presence of single or multiple genetic variants of uncertain significance, even if not allowing any specific diagnosis, correlated with a poorer response to glucocorticoids, possibly indicating a multifactorial subgroup of PFS with differential response to pharmacological treatment.
Keywords: Adolescent; Carrier Proteins; Child; Cryopyrin-Associated Periodic Syndromes; Cytoskeletal Proteins; Familial Mediterranean Fever; Female; Fever; Gene Expression Profiling; Genotype; Hereditary Autoinflammatory Diseases; Humans; Intracellular Signaling Peptides and Proteins; Logistic Models; Male; Mutation; Phosphotransferases (Alcohol Group Acceptor); Prospective Studies; Receptors, Tumor Necrosis Factor, Type I; Syndrome

Genetic studies of body mass index yield new insights for obesity biology. - Locke, Adam E; Kahali, Bratati; Berndt, Sonja I; Justice, Anne E; Pers, Tune H; Day, Felix R; Powell, Corey; Vedantam, Sailaja; Buchkovich, Martin L; Yang, Jian; Croteau-Chonka, Damien C; Esko, Tõnu; et al. (Nature, 2015)
Obesity is heritable and predisposes to many diseases. To understand the genetic basis of obesity better, here we conduct a genome-wide association study and Metabochip meta-analysis of body mass index (BMI), a measure commonly used to define obesity and assess adiposity, in up to 339,224 individuals. This analysis identifies 97 BMI-associated loci (P < 5 × 10(-8)), 56 of which are novel. Five loci demonstrate clear evidence of several independent association signals, and many loci have significant effects on other metabolic phenotypes. The 97 loci account for ∼2.7% of BMI variation, and genome-wide estimates suggest that common variation accounts for >20% of BMI variation. Pathway analyses provide strong support for a role of the central nervous system in obesity susceptibility and implicate new genes and pathways, including those related to synaptic function, glutamate signalling, insulin secretion/action, energy metabolism, lipid biology and adipogenesis.
Keywords: Adipogenesis; Adiposity; Age Factors; Body Mass Index; Continental Population Groups; Energy Metabolism; Europe; Female; Genetic Predisposition to Disease; Genome-Wide Association Study; Glutamic Acid; Humans; Insulin; Male; Obesity; Polymorphism, Single Nucleotide; Quantitative Trait Loci; Synapses

Genetic testing and genomic analysis: a debate on ethical, social and legal issues in the Arab world with a focus on Qatar. - El Shanti, Hatem; Chouchane, Lotfi; Badii, Ramin; Gallouzi, Imed Eddine; Gasparini, Paolo (J Transl Med, 2015)
In 2013 both Saudi Arabia and Qatar launched genome projects with the aim of providing information for better diagnosis, treatment and prevention of diseases and, ultimately to realize personalized medicine by sequencing hundred thousands samples. These population based genome activities raise a series of relevant ethical, legal and social issues general, related to the specific population structure as well as to the Islamic perspective on genomic analysis and genetic testing. To contribute to the debate, the Authors after reviewing the existing literature and taking advantage of their professional experience in the field and in the geographic area, discuss and provide their opinions. In particular, the Authors focus on the impact of consanguinity on population structure and disease frequency in the Arab world, on genetic testing and genomic analysis (i.e. technical aspects, impact, etc.) and on their regulations. A comparison between the Islamic perspective and the ethical, social and legal issues raised in other population contexts is also carried. In conclusion, this opinion article with an up-to-date contribution to the discussion on the relevance and impact of genomic analysis and genetic testing in the Arab world, might help in producing specific national guidelines on genetic testing and genomic analysis and help accelerate the implementation and roll out of genome projects in Muslim countries and more specifically in Qatar, and other countries of the Gulf.

Genetics of inflammatory bowel disease from multifactorial to monogenic forms. - Bianco, Anna Monica; Girardelli, Martina; Tommasini, Alberto (World J Gastroenterol, 2015)
Inflammatory bowel disease (IBD) is a group of chronic multifactorial disorders. According to a recent study, the number of IBD association loci is increased to 201, of which 37 and 27 loci contribute specifically to the development of Crohn's disease and ulcerative colitis respectively. Some IBD associated genes are involved in innate immunity, in the autophagy and in the inflammatory response such as NOD2, ATG16L1 and IL23R, while other are implicated in immune mediated disease (STAT3) and in susceptibility to mycobacterium infection (IL12B). In case of early onset of IBD (VEO-IBD) within the 6(th) year of age, the disease may be caused by mutations in genes responsible for severe monogenic disorders such as the primary immunodeficiency diseases. In this review we discuss how these monogenic disorders through different immune mechanisms can similarly be responsible of VEO-IBD phenotype. Moreover we would highlight how the identification of pathogenic genes by Next Generation Sequencing technologies can allow to obtain a rapid diagnosis and to apply specific therapies.

Genome sequencing elucidates Sardinian genetic architecture and augments association analyses for lipid and blood inflammatory markers. - Sidore, Carlo; Busonero, Fabio; Maschio, Andrea; Porcu, Eleonora; Naitza, Silvia; Zoledziewska, Magdalena; Mulas, Antonella; Pistis, Giorgio; Steri, Maristella; Danjou, Fabrice; Kwong, Alan; Ortega Del Vecchyo, Vicente Diego; et al. (Nat Genet, 2015)
We report ∼17.6 million genetic variants from whole-genome sequencing of 2,120 Sardinians; 22% are absent from previous sequencing-based compilations and are enriched for predicted functional consequences. Furthermore, ∼76,000 variants common in our sample (frequency >5%) are rare elsewhere (<0.5% in the 1000 Genomes Project). We assessed the impact of these variants on circulating lipid levels and five inflammatory biomarkers. We observe 14 signals, including 2 major new loci, for lipid levels and 19 signals, including 2 new loci, for inflammatory markers. The new associations would have been missed in analyses based on 1000 Genomes Project data, underlining the advantages of large-scale sequencing in this founder population.

Genome-wide association analysis on five isolated populations identifies variants of the HLA-DOA gene associated with white wine liking. - Pirastu, Nicola; Kooyman, Maarten; Traglia, Michela; Robino, Antonietta; Willems, Sara M; Pistis, Giorgio; Amin, Najaf; Sala, Cinzia; Karssen, Lennart C; van Duijn, Cornelia M; Toniolo, Daniela; Gasparini, Paolo (Eur J Hum Genet, 2015)
Wine is the most popular alcoholic beverage around the world and because of its importance in society has been widely studied. Understanding what drives its flavor has been a quest for decades but much is still unknown and will be determined at least in part by individual taste preferences. Recently studies in the genetics of taste have uncovered the role of different genes in the determination of food preferences giving new insight on its physiology. In this context we have performed a genome-wide association study on red and white wine liking using three isolated populations collected in Italy, and replicated our results on two additional populations coming from the Netherland and Central Asia for a total of 3885 samples. We have found a significant association (P=2.1 × 10(-8)) between white wine liking and rs9276975:C>T a polymorphism in the HLA-DOA gene encoding a non-canonical MHC II molecule, which regulates other MHC II molecules. The same association was also found with red wine liking (P=8.3 × 10(-6)). Sex-separated analysis have also revealed that the effect of HLA-DOA is twice as large in women as compared to men suggesting an interaction between this polymorphism and gender. Our results are one of the first examples of genome-wide association between liking of a commonly consumed food and gene variants. Moreover, our results suggest a role of the MHC system in the determination of food preferences opening new insight in this field in general.

Genome-wide association analysis on normal hearing function identifies PCDH20 and SLC28A3 as candidates for hearing function and loss. - Vuckovic, Dragana; Dawson, Sally; Scheffer, Deborah I; Rantanen, Taina; Morgan, Anna; Di Stazio, Mariateresa; Vozzi, Diego; Nutile, Teresa; Concas, Maria P; Biino, Ginevra; Nolan, Lisa; Bahl, Aileen; et al. (Hum Mol Genet, 2015)
Hearing loss and individual differences in normal hearing both have a substantial genetic basis. Although many new genes contributing to deafness have been identified, very little is known about genes/variants modulating the normal range of hearing ability. To fill this gap, we performed a two-stage meta-analysis on hearing thresholds (tested at 0.25, 0.5, 1, 2, 4, 8 kHz) and on pure-tone averages (low-, medium- and high-frequency thresholds grouped) in several isolated populations from Italy and Central Asia (total N = 2636). Here, we detected two genome-wide significant loci close to PCDH20 and SLC28A3 (top hits: rs78043697, P = 4.71E-10 and rs7032430, P = 2.39E-09, respectively). For both loci, we sought replication in two independent cohorts: B58C from the UK (N = 5892) and FITSA from Finland (N = 270). Both loci were successfully replicated at a nominal level of significance (P < 0.05). In order to confirm our quantitative findings, we carried out RT-PCR and reported RNA-Seq data, which showed that both genes are expressed in mouse inner ear, especially in hair cells, further suggesting them as good candidates for modulatory genes in the auditory system. Sequencing data revealed no functional variants in the coding region of PCDH20 or SLC28A3, suggesting that variation in regulatory sequences may affect expression. Overall, these results contribute to a better understanding of the complex mechanisms underlying human hearing function.

Germline mutations in ETV6 are associated with thrombocytopenia, red cell macrocytosis and predisposition to lymphoblastic leukemia. - Noetzli, Leila; Lo, Richard W; Lee-Sherick, Alisa B; Callaghan, Michael; Noris, Patrizia; Savoia, Anna; Rajpurkar, Madhvi; Jones, Kenneth; Gowan, Katherine; Balduini, Carlo L; Pecci, Alessandro; Gnan, Chiara; et al. (Nat Genet, 2015)
Some familial platelet disorders are associated with predisposition to leukemia, myelodysplastic syndrome (MDS) or dyserythropoietic anemia. We identified a family with autosomal dominant thrombocytopenia, high erythrocyte mean corpuscular volume (MCV) and two occurrences of B cell-precursor acute lymphoblastic leukemia (ALL). Whole-exome sequencing identified a heterozygous single-nucleotide change in ETV6 (ets variant 6), c.641C>T, encoding a p.Pro214Leu substitution in the central domain, segregating with thrombocytopenia and elevated MCV. A screen of 23 families with similar phenotypes identified 2 with ETV6 mutations. One family also had a mutation encoding p.Pro214Leu and one individual with ALL. The other family had a c.1252A>G transition producing a p.Arg418Gly substitution in the DNA-binding domain, with alternative splicing and exon skipping. Functional characterization of these mutations showed aberrant cellular localization of mutant and endogenous ETV6, decreased transcriptional repression and altered megakaryocyte maturation. Our findings underscore a key role for ETV6 in platelet formation and leukemia predisposition.
Keywords: Adult; Child, Preschool; DNA Mutational Analysis; Erythrocytes, Abnormal; Exome; Female; Genetic Association Studies; Genetic Predisposition to Disease; Germ-Line Mutation; HEK293 Cells; Hematologic Diseases; Humans; Male; Mutation, Missense; Pedigree; Precursor Cell Lymphoblastic Leukemia-Lymphoma; Proto-Oncogene Proteins c-ets; Repressor Proteins; Thrombocytopenia

The Global Burden of Cancer 2013. - Fitzmaurice, Christina; Dicker, Daniel; Pain, Amanda; Hamavid, Hannah; Moradi-Lakeh, Maziar; MacIntyre, Michael F; Allen, Christine; Hansen, Gillian; Woodbrook, Rachel; Wolfe, Charles; Hamadeh, Randah R; Moore, Ami; et al. (JAMA Oncol, 2015)
IMPORTANCE: Cancer is among the leading causes of death worldwide. Current estimates of cancer burden in individual countries and regions are necessary to inform local cancer control strategies. OBJECTIVE: To estimate mortality, incidence, years lived with disability (YLDs), years of life lost (YLLs), and disability-adjusted life-years (DALYs) for 28 cancers in 188 countries by sex from 1990 to 2013. EVIDENCE REVIEW: The general methodology of the Global Burden of Disease (GBD) 2013 study was used. Cancer registries were the source for cancer incidence data as well as mortality incidence (MI) ratios. Sources for cause of death data include vital registration system data, verbal autopsy studies, and other sources. The MI ratios were used to transform incidence data to mortality estimates and cause of death estimates to incidence estimates. Cancer prevalence was estimated using MI ratios as surrogates for survival data; YLDs were calculated by multiplying prevalence estimates with disability weights, which were derived from population-based surveys; YLLs were computed by multiplying the number of estimated cancer deaths at each age with a reference life expectancy; and DALYs were calculated as the sum of YLDs and YLLs. FINDINGS: In 2013 there were 14.9 million incident cancer cases, 8.2 million deaths, and 196.3 million DALYs. Prostate cancer was the leading cause for cancer incidence (1.4 million) for men and breast cancer for women (1.8 million). Tracheal, bronchus, and lung (TBL) cancer was the leading cause for cancer death in men and women, with 1.6 million deaths. For men, TBL cancer was the leading cause of DALYs (24.9 million). For women, breast cancer was the leading cause of DALYs (13.1 million). Age-standardized incidence rates (ASIRs) per 100 000 and age-standardized death rates (ASDRs) per 100 000 for both sexes in 2013 were higher in developing vs developed countries for stomach cancer (ASIR, 17 vs 14; ASDR, 15 vs 11), liver cancer (ASIR, 15 vs 7; ASDR, 16 vs 7), esophageal cancer (ASIR, 9 vs 4; ASDR, 9 vs 4), cervical cancer (ASIR, 8 vs 5; ASDR, 4 vs 2), lip and oral cavity cancer (ASIR, 7 vs 6; ASDR, 2 vs 2), and nasopharyngeal cancer (ASIR, 1.5 vs 0.4; ASDR, 1.2 vs 0.3). Between 1990 and 2013, ASIRs for all cancers combined (except nonmelanoma skin cancer and Kaposi sarcoma) increased by more than 10% in 113 countries and decreased by more than 10% in 12 of 188 countries. CONCLUSIONS AND RELEVANCE: Cancer poses a major threat to public health worldwide, and incidence rates have increased in most countries since 1990. The trend is a particular threat to developing nations with health systems that are ill-equipped to deal with complex and expensive cancer treatments. The annual update on the Global Burden of Cancer will provide all stakeholders with timely estimates to guide policy efforts in cancer prevention, screening, treatment, and palliation.

Global, regional, and national age-sex specific all-cause and cause-specific mortality for 240 causes of death, 1990-2013: a systematic analysis for the Global Burden of Disease Study 2013. (Lancet, 2015)
BACKGROUND: Up-to-date evidence on levels and trends for age-sex-specific all-cause and cause-specific mortality is essential for the formation of global, regional, and national health policies. In the Global Burden of Disease Study 2013 (GBD 2013) we estimated yearly deaths for 188 countries between 1990, and 2013. We used the results to assess whether there is epidemiological convergence across countries. METHODS: We estimated age-sex-specific all-cause mortality using the GBD 2010 methods with some refinements to improve accuracy applied to an updated database of vital registration, survey, and census data. We generally estimated cause of death as in the GBD 2010. Key improvements included the addition of more recent vital registration data for 72 countries, an updated verbal autopsy literature review, two new and detailed data systems for China, and more detail for Mexico, UK, Turkey, and Russia. We improved statistical models for garbage code redistribution. We used six different modelling strategies across the 240 causes; cause of death ensemble modelling (CODEm) was the dominant strategy for causes with sufficient information. Trends for Alzheimer's disease and other dementias were informed by meta-regression of prevalence studies. For pathogen-specific causes of diarrhoea and lower respiratory infections we used a counterfactual approach. We computed two measures of convergence (inequality) across countries: the average relative difference across all pairs of countries (Gini coefficient) and the average absolute difference across countries. To summarise broad findings, we used multiple decrement life-tables to decompose probabilities of death from birth to exact age 15 years, from exact age 15 years to exact age 50 years, and from exact age 50 years to exact age 75 years, and life expectancy at birth into major causes. For all quantities reported, we computed 95% uncertainty intervals (UIs). We constrained cause-specific fractions within each age-sex-country-year group to sum to all-cause mortality based on draws from the uncertainty distributions. FINDINGS: Global life expectancy for both sexes increased from 65.3 years (UI 65.0-65.6) in 1990, to 71.5 years (UI 71.0-71.9) in 2013, while the number of deaths increased from 47.5 million (UI 46.8-48.2) to 54.9 million (UI 53.6-56.3) over the same interval. Global progress masked variation by age and sex: for children, average absolute differences between countries decreased but relative differences increased. For women aged 25-39 years and older than 75 years and for men aged 20-49 years and 65 years and older, both absolute and relative differences increased. Decomposition of global and regional life expectancy showed the prominent role of reductions in age-standardised death rates for cardiovascular diseases and cancers in high-income regions, and reductions in child deaths from diarrhoea, lower respiratory infections, and neonatal causes in low-income regions. HIV/AIDS reduced life expectancy in southern sub-Saharan Africa. For most communicable causes of death both numbers of deaths and age-standardised death rates fell whereas for most non-communicable causes, demographic shifts have increased numbers of deaths but decreased age-standardised death rates. Global deaths from injury increased by 10.7%, from 4.3 million deaths in 1990 to 4.8 million in 2013; but age-standardised rates declined over the same period by 21%. For some causes of more than 100,000 deaths per year in 2013, age-standardised death rates increased between 1990 and 2013, including HIV/AIDS, pancreatic cancer, atrial fibrillation and flutter, drug use disorders, diabetes, chronic kidney disease, and sickle-cell anaemias. Diarrhoeal diseases, lower respiratory infections, neonatal causes, and malaria are still in the top five causes of death in children younger than 5 years. The most important pathogens are rotavirus for diarrhoea and pneumococcus for lower respiratory infections. Country-specific probabilities of death over three phases of life were substantially varied between and within regions. INTERPRETATION: For most countries, the general pattern of reductions in age-sex specific mortality has been associated with a progressive shift towards a larger share of the remaining deaths caused by non-communicable disease and injuries. Assessing epidemiological convergence across countries depends on whether an absolute or relative measure of inequality is used. Nevertheless, age-standardised death rates for seven substantial causes are increasing, suggesting the potential for reversals in some countries. Important gaps exist in the empirical data for cause of death estimates for some countries; for example, no national data for India are available for the past decade. FUNDING: Bill & Melinda Gates Foundation.
Keywords: Adolescent; Adult; Aged; Aged, 80 and over; Cause of Death; Child; Child Mortality; Child, Preschool; Databases, Factual; Female; Global Health; Humans; Infant; Infant, Newborn; Life Expectancy; Life Tables; Male; Middle Aged; Models, Statistical; Mortality; Sex Distribution; Young Adult

Global, regional, and national comparative risk assessment of 79 behavioural, environmental and occupational, and metabolic risks or clusters of risks in 188 countries, 1990-2013: a systematic analysis for the Global Burden of Disease Study 2013. - Forouzanfar, Mohammad H; Alexander, Lily; Anderson, H Ross; Bachman, Victoria F; Biryukov, Stan; Brauer, Michael; Burnett, Richard; Casey, Daniel; Coates, Matthew M; Cohen, Aaron; Delwiche, Kristen; Estep, Kara; et al. (Lancet, 2015)
BACKGROUND: The Global Burden of Disease, Injuries, and Risk Factor study 2013 (GBD 2013) is the first of a series of annual updates of the GBD. Risk factor quantification, particularly of modifiable risk factors, can help to identify emerging threats to population health and opportunities for prevention. The GBD 2013 provides a timely opportunity to update the comparative risk assessment with new data for exposure, relative risks, and evidence on the appropriate counterfactual risk distribution. METHODS: Attributable deaths, years of life lost, years lived with disability, and disability-adjusted life-years (DALYs) have been estimated for 79 risks or clusters of risks using the GBD 2010 methods. Risk-outcome pairs meeting explicit evidence criteria were assessed for 188 countries for the period 1990-2013 by age and sex using three inputs: risk exposure, relative risks, and the theoretical minimum risk exposure level (TMREL). Risks are organised into a hierarchy with blocks of behavioural, environmental and occupational, and metabolic risks at the first level of the hierarchy. The next level in the hierarchy includes nine clusters of related risks and two individual risks, with more detail provided at levels 3 and 4 of the hierarchy. Compared with GBD 2010, six new risk factors have been added: handwashing practices, occupational exposure to trichloroethylene, childhood wasting, childhood stunting, unsafe sex, and low glomerular filtration rate. For most risks, data for exposure were synthesised with a Bayesian meta-regression method, DisMod-MR 2.0, or spatial-temporal Gaussian process regression. Relative risks were based on meta-regressions of published cohort and intervention studies. Attributable burden for clusters of risks and all risks combined took into account evidence on the mediation of some risks such as high body-mass index (BMI) through other risks such as high systolic blood pressure and high cholesterol. FINDINGS: All risks combined account for 57·2% (95% uncertainty interval [UI] 55·8-58·5) of deaths and 41·6% (40·1-43·0) of DALYs. Risks quantified account for 87·9% (86·5-89·3) of cardiovascular disease DALYs, ranging to a low of 0% for neonatal disorders and neglected tropical diseases and malaria. In terms of global DALYs in 2013, six risks or clusters of risks each caused more than 5% of DALYs: dietary risks accounting for 11·3 million deaths and 241·4 million DALYs, high systolic blood pressure for 10·4 million deaths and 208·1 million DALYs, child and maternal malnutrition for 1·7 million deaths and 176·9 million DALYs, tobacco smoke for 6·1 million deaths and 143·5 million DALYs, air pollution for 5·5 million deaths and 141·5 million DALYs, and high BMI for 4·4 million deaths and 134·0 million DALYs. Risk factor patterns vary across regions and countries and with time. In sub-Saharan Africa, the leading risk factors are child and maternal malnutrition, unsafe sex, and unsafe water, sanitation, and handwashing. In women, in nearly all countries in the Americas, north Africa, and the Middle East, and in many other high-income countries, high BMI is the leading risk factor, with high systolic blood pressure as the leading risk in most of Central and Eastern Europe and south and east Asia. For men, high systolic blood pressure or tobacco use are the leading risks in nearly all high-income countries, in north Africa and the Middle East, Europe, and Asia. For men and women, unsafe sex is the leading risk in a corridor from Kenya to South Africa. INTERPRETATION: Behavioural, environmental and occupational, and metabolic risks can explain half of global mortality and more than one-third of global DALYs providing many opportunities for prevention. Of the larger risks, the attributable burden of high BMI has increased in the past 23 years. In view of the prominence of behavioural risk factors, behavioural and social science research on interventions for these risks should be strengthened. Many prevention and primary care policy options are available now to act on key risks. FUNDING: Bill & Melinda Gates Foundation.

Global, regional, and national disability-adjusted life years (DALYs) for 306 diseases and injuries and healthy life expectancy (HALE) for 188 countries, 1990-2013: quantifying the epidemiological transition. - Murray, Christopher J L; Barber, Ryan M; Foreman, Kyle J; Abbasoglu Ozgoren, Ayse; Abd-Allah, Foad; Abera, Semaw F; Aboyans, Victor; Abraham, Jerry P; Abubakar, Ibrahim; Abu-Raddad, Laith J; Abu-Rmeileh, Niveen M; Achoki, Tom; et al. (Lancet, 2015)
BACKGROUND: The Global Burden of Disease Study 2013 (GBD 2013) aims to bring together all available epidemiological data using a coherent measurement framework, standardised estimation methods, and transparent data sources to enable comparisons of health loss over time and across causes, age-sex groups, and countries. The GBD can be used to generate summary measures such as disability-adjusted life-years (DALYs) and healthy life expectancy (HALE) that make possible comparative assessments of broad epidemiological patterns across countries and time. These summary measures can also be used to quantify the component of variation in epidemiology that is related to sociodemographic development. METHODS: We used the published GBD 2013 data for age-specific mortality, years of life lost due to premature mortality (YLLs), and years lived with disability (YLDs) to calculate DALYs and HALE for 1990, 1995, 2000, 2005, 2010, and 2013 for 188 countries. We calculated HALE using the Sullivan method; 95% uncertainty intervals (UIs) represent uncertainty in age-specific death rates and YLDs per person for each country, age, sex, and year. We estimated DALYs for 306 causes for each country as the sum of YLLs and YLDs; 95% UIs represent uncertainty in YLL and YLD rates. We quantified patterns of the epidemiological transition with a composite indicator of sociodemographic status, which we constructed from income per person, average years of schooling after age 15 years, and the total fertility rate and mean age of the population. We applied hierarchical regression to DALY rates by cause across countries to decompose variance related to the sociodemographic status variable, country, and time. FINDINGS: Worldwide, from 1990 to 2013, life expectancy at birth rose by 6·2 years (95% UI 5·6-6·6), from 65·3 years (65·0-65·6) in 1990 to 71·5 years (71·0-71·9) in 2013, HALE at birth rose by 5·4 years (4·9-5·8), from 56·9 years (54·5-59·1) to 62·3 years (59·7-64·8), total DALYs fell by 3·6% (0·3-7·4), and age-standardised DALY rates per 100 000 people fell by 26·7% (24·6-29·1). For communicable, maternal, neonatal, and nutritional disorders, global DALY numbers, crude rates, and age-standardised rates have all declined between 1990 and 2013, whereas for non-communicable diseases, global DALYs have been increasing, DALY rates have remained nearly constant, and age-standardised DALY rates declined during the same period. From 2005 to 2013, the number of DALYs increased for most specific non-communicable diseases, including cardiovascular diseases and neoplasms, in addition to dengue, food-borne trematodes, and leishmaniasis; DALYs decreased for nearly all other causes. By 2013, the five leading causes of DALYs were ischaemic heart disease, lower respiratory infections, cerebrovascular disease, low back and neck pain, and road injuries. Sociodemographic status explained more than 50% of the variance between countries and over time for diarrhoea, lower respiratory infections, and other common infectious diseases; maternal disorders; neonatal disorders; nutritional deficiencies; other communicable, maternal, neonatal, and nutritional diseases; musculoskeletal disorders; and other non-communicable diseases. However, sociodemographic status explained less than 10% of the variance in DALY rates for cardiovascular diseases; chronic respiratory diseases; cirrhosis; diabetes, urogenital, blood, and endocrine diseases; unintentional injuries; and self-harm and interpersonal violence. Predictably, increased sociodemographic status was associated with a shift in burden from YLLs to YLDs, driven by declines in YLLs and increases in YLDs from musculoskeletal disorders, neurological disorders, and mental and substance use disorders. In most country-specific estimates, the increase in life expectancy was greater than that in HALE. Leading causes of DALYs are highly variable across countries. INTERPRETATION: Global health is improving. Population growth and ageing have driven up numbers of DALYs, but crude rates have remained relatively constant, showing that progress in health does not mean fewer demands on health systems. The notion of an epidemiological transition--in which increasing sociodemographic status brings structured change in disease burden--is useful, but there is tremendous variation in burden of disease that is not associated with sociodemographic status. This further underscores the need for country-specific assessments of DALYs and HALE to appropriately inform health policy decisions and attendant actions. FUNDING: Bill & Melinda Gates Foundation.
Keywords: Aged; Chronic Disease; Communicable Diseases; Female; Global Health; Health Transition; Humans; Life Expectancy; Male; Middle Aged; Mortality, Premature; Quality-Adjusted Life Years; Socioeconomic Factors; Wounds and Injuries

Global, regional, and national incidence, prevalence, and years lived with disability for 301 acute and chronic diseases and injuries in 188 countries, 1990-2013: a systematic analysis for the Global Burden of Disease Study 2013. (Lancet, 2015)
BACKGROUND: Up-to-date evidence about levels and trends in disease and injury incidence, prevalence, and years lived with disability (YLDs) is an essential input into global, regional, and national health policies. In the Global Burden of Disease Study 2013 (GBD 2013), we estimated these quantities for acute and chronic diseases and injuries for 188 countries between 1990 and 2013. METHODS: Estimates were calculated for disease and injury incidence, prevalence, and YLDs using GBD 2010 methods with some important refinements. Results for incidence of acute disorders and prevalence of chronic disorders are new additions to the analysis. Key improvements include expansion to the cause and sequelae list, updated systematic reviews, use of detailed injury codes, improvements to the Bayesian meta-regression method (DisMod-MR), and use of severity splits for various causes. An index of data representativeness, showing data availability, was calculated for each cause and impairment during three periods globally and at the country level for 2013. In total, 35 620 distinct sources of data were used and documented to calculated estimates for 301 diseases and injuries and 2337 sequelae. The comorbidity simulation provides estimates for the number of sequelae, concurrently, by individuals by country, year, age, and sex. Disability weights were updated with the addition of new population-based survey data from four countries. FINDINGS: Disease and injury were highly prevalent; only a small fraction of individuals had no sequelae. Comorbidity rose substantially with age and in absolute terms from 1990 to 2013. Incidence of acute sequelae were predominantly infectious diseases and short-term injuries, with over 2 billion cases of upper respiratory infections and diarrhoeal disease episodes in 2013, with the notable exception of tooth pain due to permanent caries with more than 200 million incident cases in 2013. Conversely, leading chronic sequelae were largely attributable to non-communicable diseases, with prevalence estimates for asymptomatic permanent caries and tension-type headache of 2·4 billion and 1·6 billion, respectively. The distribution of the number of sequelae in populations varied widely across regions, with an expected relation between age and disease prevalence. YLDs for both sexes increased from 537·6 million in 1990 to 764·8 million in 2013 due to population growth and ageing, whereas the age-standardised rate decreased little from 114·87 per 1000 people to 110·31 per 1000 people between 1990 and 2013. Leading causes of YLDs included low back pain and major depressive disorder among the top ten causes of YLDs in every country. YLD rates per person, by major cause groups, indicated the main drivers of increases were due to musculoskeletal, mental, and substance use disorders, neurological disorders, and chronic respiratory diseases; however HIV/AIDS was a notable driver of increasing YLDs in sub-Saharan Africa. Also, the proportion of disability-adjusted life years due to YLDs increased globally from 21·1% in 1990 to 31·2% in 2013. INTERPRETATION: Ageing of the world's population is leading to a substantial increase in the numbers of individuals with sequelae of diseases and injuries. Rates of YLDs are declining much more slowly than mortality rates. The non-fatal dimensions of disease and injury will require more and more attention from health systems. The transition to non-fatal outcomes as the dominant source of burden of disease is occurring rapidly outside of sub-Saharan Africa. Our results can guide future health initiatives through examination of epidemiological trends and a better understanding of variation across countries. FUNDING: Bill & Melinda Gates Foundation.
Keywords: Acute Disease; Adolescent; Adult; Age Distribution; Aged; Aged, 80 and over; Child; Child, Preschool; Chronic Disease; Cost of Illness; Developed Countries; Developing Countries; Disabled Persons; Female; Global Health; Humans; Incidence; Infant; Infant, Newborn; Male; Middle Aged; Neglected Diseases; Prevalence; Residence Characteristics; Sex Distribution; Wounds and Injuries; Young Adult

Glucocorticoid pharmacogenetics in pediatric idiopathic nephrotic syndrome. - Cuzzoni, Eva; De Iudicibus, Sara; Franca, Raffaella; Stocco, Gabriele; Lucafò, Marianna; Pelin, Marco; Favretto, Diego; Pasini, Andrea; Montini, Giovanni; Decorti, Giuliana (Pharmacogenomics, 2015)
Idiopathic nephrotic syndrome represents the most common type of primary glomerular disease in children: glucocorticoids (GCs) are the first-line therapy, even if considerable interindividual differences in thepir efficacy and side effects have been reported. Immunosuppressive and anti-inflammatory effects of these drugs are mainly due to the GC-mediated transcription regulation of pro- and anti-inflammatory genes. This mechanism of action is the result of a complex multistep pathway that involves the glucocorticoid receptor and several other proteins, encoded by polymorphic genes. Aim of this review is to highlight the current knowledge on genetic variants that could affect GC response, particularly focusing on children with idiopathic nephrotic syndrome.

GRID2 a novel gene possibly associated with mevalonate kinase deficiency. - Moura, Ronald; Tricarico, Paola Maura; Campos Coelho, Antonio Victor; Crovella, Sergio (Rheumatol Int, 2015)
Mevalonate kinase deficiency (MKD) is a rare autosomal disease caused by mutations in the mevalonate kinase gene (MVK). The genotype-phenotype correlation is sometimes problematic due to the great genetic and clinical heterogeneity; so we hypothesize that genes other than MVK are able to modulate MKD clinical phenotypes. This hypothesis was tested by analyzing the exome of 22 patients with MKD all carrying MVK gene mutations, and 20 patients with recurrent fevers (RF) not carrying MVK mutations. Our preliminary findings suggest a possible role of GRID2 in the susceptibility to develop MKD. GRID2 gene (4q22.2), encoding for human glutamate receptor delta-2, associated with MKD: The rs1450500 SNP was differently distributed in patients with MKD with respect to those with RF. Being aware of the small number of patients analyzed, we hypothesized a possible role for GRID2 as possible phenotype modifier in MKD patients, especially in those with severe phenotypes.

A general approach for haplotype phasing across the full spectrum of relatedness. - O'Connell, Jared; Gurdasani, Deepti; Delaneau, Olivier; Pirastu, Nicola; Ulivi, Sheila; Cocca, Massimiliano; Traglia, Michela; Huang, Jie; Huffman, Jennifer E; Rudan, Igor; McQuillan, Ruth; Fraser, Ross M; et al. (PLoS Genet, 2014)
Many existing cohorts contain a range of relatedness between genotyped individuals, either by design or by chance. Haplotype estimation in such cohorts is a central step in many downstream analyses. Using genotypes from six cohorts from isolated populations and two cohorts from non-isolated populations, we have investigated the performance of different phasing methods designed for nominally 'unrelated' individuals. We find that SHAPEIT2 produces much lower switch error rates in all cohorts compared to other methods, including those designed specifically for isolated populations. In particular, when large amounts of IBD sharing is present, SHAPEIT2 infers close to perfect haplotypes. Based on these results we have developed a general strategy for phasing cohorts with any level of implicit or explicit relatedness between individuals. First SHAPEIT2 is run ignoring all explicit family information. We then apply a novel HMM method (duoHMM) to combine the SHAPEIT2 haplotypes with any family information to infer the inheritance pattern of each meiosis at all sites across each chromosome. This allows the correction of switch errors, detection of recombination events and genotyping errors. We show that the method detects numbers of recombination events that align very well with expectations based on genetic maps, and that it infers far fewer spurious recombination events than Merlin. The method can also detect genotyping errors and infer recombination events in otherwise uninformative families, such as trios and duos. The detected recombination events can be used in association scans for recombination phenotypes. The method provides a simple and unified approach to haplotype estimation, that will be of interest to researchers in the fields of human, animal and plant genetics.
Keywords: Chromosome Mapping; Cohort Effect; Family; Genotype; Haplotypes; Humans; Models, Genetic; Pedigree; Phenotype; Recombination, Genetic

Genetic association study of QT interval highlights role for calcium signaling pathways in myocardial repolarization. - Arking, Dan E; Pulit, Sara L; Crotti, Lia; van der Harst, Pim; Munroe, Patricia B; Koopmann, Tamara T; Sotoodehnia, Nona; Rossin, Elizabeth J; Morley, Michael; Wang, Xinchen; Johnson, Andrew D; Lundby, Alicia; et al. (Nat Genet, 2014)
The QT interval, an electrocardiographic measure reflecting myocardial repolarization, is a heritable trait. QT prolongation is a risk factor for ventricular arrhythmias and sudden cardiac death (SCD) and could indicate the presence of the potentially lethal mendelian long-QT syndrome (LQTS). Using a genome-wide association and replication study in up to 100,000 individuals, we identified 35 common variant loci associated with QT interval that collectively explain ∼8-10% of QT-interval variation and highlight the importance of calcium regulation in myocardial repolarization. Rare variant analysis of 6 new QT interval-associated loci in 298 unrelated probands with LQTS identified coding variants not found in controls but of uncertain causality and therefore requiring validation. Several newly identified loci encode proteins that physically interact with other recognized repolarization proteins. Our integration of common variant association, expression and orthogonal protein-protein interaction screens provides new insights into cardiac electrophysiology and identifies new candidate genes for ventricular arrhythmias, LQTS and SCD.
Keywords: Adult; Aged; Arrhythmias, Cardiac; Calcium Signaling; Death, Sudden, Cardiac; Electrocardiography; Female; Genetic Predisposition to Disease; Genome-Wide Association Study; Genotype; Heart Ventricles; Humans; Long QT Syndrome; Male; Middle Aged; Myocardium; Polymorphism, Single Nucleotide

Genetic landscape of populations along the Silk Road: admixture and migration patterns. - Mezzavilla, Massimo; Vozzi, Diego; Pirastu, Nicola; Girotto, Giorgia; d'Adamo, Pio; Gasparini, Paolo; Colonna, Vincenza (BMC Genet, 2014)
BACKGROUND: The ancient Silk Road has been a trading route between Europe and Central Asia from the 2(nd) century BCE to the 15(th) century CE. While most populations on this route have been characterized, the genetic background of others remains poorly understood, and little is known about past migration patterns. The scientific expedition "Marco Polo" has recently collected genetic and phenotypic data in six regions (Georgia, Armenia, Azerbaijan, Uzbekistan, Kazakhstan, Tajikistan) along the Silk Road to study the genetics of a number of phenotypes. RESULTS: We characterized the genetic structure of these populations within a worldwide context. We observed a West-East subdivision albeit the existence of a genetic component shared within Central Asia and nearby populations from Europe and Near East. We observed a contribution of up to 50% from Europe and Asia to most of the populations that have been analyzed. The contribution from Asia dates back to ~25 generations and is limited to the Eastern Silk Road. Time and direction of this contribution are consistent with the Mongolian expansion era. CONCLUSIONS: We clarified the genetic structure of six populations from Central Asia and suggested a complex pattern of gene flow among them. We provided a map of migration events in time and space and we quantified exchanges among populations. Altogether these novel findings will support the future studies aimed at understanding the genetics of the phenotypes that have been collected during the Marco Polo campaign, they will provide insights into the history of these populations, and they will be useful to reconstruct the developments and events that have shaped modern Eurasians genomes.
Keywords: Asian Continental Ancestry Group; Commonwealth of Independent States; European Continental Ancestry Group; Gene Flow; Homozygote; Human Migration; Humans; Phenotype; Polymorphism, Single Nucleotide; Principal Component Analysis; Sequence Analysis, DNA

Genome-wide association study of sexual maturation in males and females highlights a role for body mass and menarche loci in male puberty. - Cousminer, Diana L; Stergiakouli, Evangelia; Berry, Diane J; Ang, Wei; Groen-Blokhuis, Maria M; Körner, Antje; Siitonen, Niina; Ntalla, Ioanna; Marinelli, Marcella; Perry, John R B; Kettunen, Johannes; Jansen, Rick; et al. (Hum Mol Genet, 2014)
Little is known about genes regulating male puberty. Further, while many identified pubertal timing variants associate with age at menarche, a late manifestation of puberty, and body mass, little is known about these variants' relationship to pubertal initiation or tempo. To address these questions, we performed genome-wide association meta-analysis in over 11 000 European samples with data on early pubertal traits, male genital and female breast development, measured by the Tanner scale. We report the first genome-wide significant locus for male sexual development upstream of myocardin-like 2 (MKL2) (P = 8.9 × 10(-9)), a menarche locus tagging a developmental pathway linking earlier puberty with reduced pubertal growth (P = 4.6 × 10(-5)) and short adult stature (p = 7.5 × 10(-6)) in both males and females. Furthermore, our results indicate that a proportion of menarche loci are important for pubertal initiation in both sexes. Consistent with epidemiological correlations between increased prepubertal body mass and earlier pubertal timing in girls, body mass index (BMI)-increasing alleles correlated with earlier breast development. In boys, some BMI-increasing alleles associated with earlier, and others with delayed, sexual development; these genetic results mimic the controversy in epidemiological studies, some of which show opposing correlations between prepubertal BMI and male puberty. Our results contribute to our understanding of the pubertal initiation program in both sexes and indicate that although mechanisms regulating pubertal onset in males and females may largely be shared, the relationship between body mass and pubertal timing in boys may be complex and requires further genetic studies.

A girl with photosensitivity and hepatic steatosis. - Pavan, Matteo; Gortani, Giulia; Rubinato, Elisa; Faletra, Flavio; Pastore, Serena; Ventura, Alessandro (J Pediatr, 2014)
Keywords: Child; Diagnosis, Differential; Fatty Liver; Female; Humans; Photosensitivity Disorders; Protoporphyria, Erythropoietic

Global, regional, and national incidence and mortality for HIV, tuberculosis, and malaria during 1990-2013: a systematic analysis for the Global Burden of Disease Study 2013. - Murray, Christopher J L; Ortblad, Katrina F; Guinovart, Caterina; Lim, Stephen S; Wolock, Timothy M; Roberts, D Allen; Dansereau, Emily A; Graetz, Nicholas; Barber, Ryan M; Brown, Jonathan C; Wang, Haidong; Duber, Herbert C; et al. (Lancet, 2014)
BACKGROUND: The Millennium Declaration in 2000 brought special global attention to HIV, tuberculosis, and malaria through the formulation of Millennium Development Goal (MDG) 6. The Global Burden of Disease 2013 study provides a consistent and comprehensive approach to disease estimation for between 1990 and 2013, and an opportunity to assess whether accelerated progress has occured since the Millennium Declaration. METHODS: To estimate incidence and mortality for HIV, we used the UNAIDS Spectrum model appropriately modified based on a systematic review of available studies of mortality with and without antiretroviral therapy (ART). For concentrated epidemics, we calibrated Spectrum models to fit vital registration data corrected for misclassification of HIV deaths. In generalised epidemics, we minimised a loss function to select epidemic curves most consistent with prevalence data and demographic data for all-cause mortality. We analysed counterfactual scenarios for HIV to assess years of life saved through prevention of mother-to-child transmission (PMTCT) and ART. For tuberculosis, we analysed vital registration and verbal autopsy data to estimate mortality using cause of death ensemble modelling. We analysed data for corrected case-notifications, expert opinions on the case-detection rate, prevalence surveys, and estimated cause-specific mortality using Bayesian meta-regression to generate consistent trends in all parameters. We analysed malaria mortality and incidence using an updated cause of death database, a systematic analysis of verbal autopsy validation studies for malaria, and recent studies (2010-13) of incidence, drug resistance, and coverage of insecticide-treated bednets. FINDINGS: Globally in 2013, there were 1·8 million new HIV infections (95% uncertainty interval 1·7 million to 2·1 million), 29·2 million prevalent HIV cases (28·1 to 31·7), and 1·3 million HIV deaths (1·3 to 1·5). At the peak of the epidemic in 2005, HIV caused 1·7 million deaths (1·6 million to 1·9 million). Concentrated epidemics in Latin America and eastern Europe are substantially smaller than previously estimated. Through interventions including PMTCT and ART, 19·1 million life-years (16·6 million to 21·5 million) have been saved, 70·3% (65·4 to 76·1) in developing countries. From 2000 to 2011, the ratio of development assistance for health for HIV to years of life saved through intervention was US$4498 in developing countries. Including in HIV-positive individuals, all-form tuberculosis incidence was 7·5 million (7·4 million to 7·7 million), prevalence was 11·9 million (11·6 million to 12·2 million), and number of deaths was 1·4 million (1·3 million to 1·5 million) in 2013. In the same year and in only individuals who were HIV-negative, all-form tuberculosis incidence was 7·1 million (6·9 million to 7·3 million), prevalence was 11·2 million (10·8 million to 11·6 million), and number of deaths was 1·3 million (1·2 million to 1·4 million). Annualised rates of change (ARC) for incidence, prevalence, and death became negative after 2000. Tuberculosis in HIV-negative individuals disproportionately occurs in men and boys (versus women and girls); 64·0% of cases (63·6 to 64·3) and 64·7% of deaths (60·8 to 70·3). Globally, malaria cases and deaths grew rapidly from 1990 reaching a peak of 232 million cases (143 million to 387 million) in 2003 and 1·2 million deaths (1·1 million to 1·4 million) in 2004. Since 2004, child deaths from malaria in sub-Saharan Africa have decreased by 31·5% (15·7 to 44·1). Outside of Africa, malaria mortality has been steadily decreasing since 1990. INTERPRETATION: Our estimates of the number of people living with HIV are 18·7% smaller than UNAIDS's estimates in 2012. The number of people living with malaria is larger than estimated by WHO. The number of people living with HIV, tuberculosis, or malaria have all decreased since 2000. At the global level, upward trends for malaria and HIV deaths have been reversed and declines in tuberculosis deaths have accelerated. 101 countries (74 of which are developing) still have increasing HIV incidence. Substantial progress since the Millennium Declaration is an encouraging sign of the effect of global action. FUNDING: Bill & Melinda Gates Foundation.
Keywords: Age Distribution; Epidemics; Female; Global Health; HIV Infections; Humans; Incidence; Malaria; Male; Mortality; Organizational Objectives; Sex Distribution; Tuberculosis

Global, regional, and national levels and causes of maternal mortality during 1990-2013: a systematic analysis for the Global Burden of Disease Study 2013. - Kassebaum, Nicholas J; Bertozzi-Villa, Amelia; Coggeshall, Megan S; Shackelford, Katya A; Steiner, Caitlyn; Heuton, Kyle R; Gonzalez-Medina, Diego; Barber, Ryan; Huynh, Chantal; Dicker, Daniel; Templin, Tara; Wolock, Timothy M; et al. (Lancet, 2014)
BACKGROUND: The fifth Millennium Development Goal (MDG 5) established the goal of a 75% reduction in the maternal mortality ratio (MMR; number of maternal deaths per 100,000 livebirths) between 1990 and 2015. We aimed to measure levels and track trends in maternal mortality, the key causes contributing to maternal death, and timing of maternal death with respect to delivery. METHODS: We used robust statistical methods including the Cause of Death Ensemble model (CODEm) to analyse a database of data for 7065 site-years and estimate the number of maternal deaths from all causes in 188 countries between 1990 and 2013. We estimated the number of pregnancy-related deaths caused by HIV on the basis of a systematic review of the relative risk of dying during pregnancy for HIV-positive women compared with HIV-negative women. We also estimated the fraction of these deaths aggravated by pregnancy on the basis of a systematic review. To estimate the numbers of maternal deaths due to nine different causes, we identified 61 sources from a systematic review and 943 site-years of vital registration data. We also did a systematic review of reports about the timing of maternal death, identifying 142 sources to use in our analysis. We developed estimates for each country for 1990-2013 using Bayesian meta-regression. We estimated 95% uncertainty intervals (UIs) for all values. FINDINGS: 292,982 (95% UI 261,017-327,792) maternal deaths occurred in 2013, compared with 376,034 (343,483-407,574) in 1990. The global annual rate of change in the MMR was -0·3% (-1·1 to 0·6) from 1990 to 2003, and -2·7% (-3·9 to -1·5) from 2003 to 2013, with evidence of continued acceleration. MMRs reduced consistently in south, east, and southeast Asia between 1990 and 2013, but maternal deaths increased in much of sub-Saharan Africa during the 1990s. 2070 (1290-2866) maternal deaths were related to HIV in 2013, 0·4% (0·2-0·6) of the global total. MMR was highest in the oldest age groups in both 1990 and 2013. In 2013, most deaths occurred intrapartum or postpartum. Causes varied by region and between 1990 and 2013. We recorded substantial variation in the MMR by country in 2013, from 956·8 (685·1-1262·8) in South Sudan to 2·4 (1·6-3·6) in Iceland. INTERPRETATION: Global rates of change suggest that only 16 countries will achieve the MDG 5 target by 2015. Accelerated reductions since the Millennium Declaration in 2000 coincide with increased development assistance for maternal, newborn, and child health. Setting of targets and associated interventions for after 2015 will need careful consideration of regions that are making slow progress, such as west and central Africa. FUNDING: Bill & Melinda Gates Foundation.
Keywords: Age Distribution; Cause of Death; Female; Global Health; HIV Infections; Humans; Maternal Mortality; Models, Statistical; Organizational Objectives; Pregnancy; Pregnancy Complications, Infectious; Risk Factors; Socioeconomic Factors; Time Factors

Global, regional, and national levels of neonatal, infant, and under-5 mortality during 1990-2013: a systematic analysis for the Global Burden of Disease Study 2013. - Wang, Haidong; Liddell, Chelsea A; Coates, Matthew M; Mooney, Meghan D; Levitz, Carly E; Schumacher, Austin E; Apfel, Henry; Iannarone, Marissa; Phillips, Bryan; Lofgren, Katherine T; Sandar, Logan; Dorrington, Rob E; et al. (Lancet, 2014)
BACKGROUND: Remarkable financial and political efforts have been focused on the reduction of child mortality during the past few decades. Timely measurements of levels and trends in under-5 mortality are important to assess progress towards the Millennium Development Goal 4 (MDG 4) target of reduction of child mortality by two thirds from 1990 to 2015, and to identify models of success. METHODS: We generated updated estimates of child mortality in early neonatal (age 0-6 days), late neonatal (7-28 days), postneonatal (29-364 days), childhood (1-4 years), and under-5 (0-4 years) age groups for 188 countries from 1970 to 2013, with more than 29,000 survey, census, vital registration, and sample registration datapoints. We used Gaussian process regression with adjustments for bias and non-sampling error to synthesise the data for under-5 mortality for each country, and a separate model to estimate mortality for more detailed age groups. We used explanatory mixed effects regression models to assess the association between under-5 mortality and income per person, maternal education, HIV child death rates, secular shifts, and other factors. To quantify the contribution of these different factors and birth numbers to the change in numbers of deaths in under-5 age groups from 1990 to 2013, we used Shapley decomposition. We used estimated rates of change between 2000 and 2013 to construct under-5 mortality rate scenarios out to 2030. FINDINGS: We estimated that 6·3 million (95% UI 6·0-6·6) children under-5 died in 2013, a 64% reduction from 17·6 million (17·1-18·1) in 1970. In 2013, child mortality rates ranged from 152·5 per 1000 livebirths (130·6-177·4) in Guinea-Bissau to 2·3 (1·8-2·9) per 1000 in Singapore. The annualised rates of change from 1990 to 2013 ranged from -6·8% to 0·1%. 99 of 188 countries, including 43 of 48 countries in sub-Saharan Africa, had faster decreases in child mortality during 2000-13 than during 1990-2000. In 2013, neonatal deaths accounted for 41·6% of under-5 deaths compared with 37·4% in 1990. Compared with 1990, in 2013, rising numbers of births, especially in sub-Saharan Africa, led to 1·4 million more child deaths, and rising income per person and maternal education led to 0·9 million and 2·2 million fewer deaths, respectively. Changes in secular trends led to 4·2 million fewer deaths. Unexplained factors accounted for only -1% of the change in child deaths. In 30 developing countries, decreases since 2000 have been faster than predicted attributable to income, education, and secular shift alone. INTERPRETATION: Only 27 developing countries are expected to achieve MDG 4. Decreases since 2000 in under-5 mortality rates are accelerating in many developing countries, especially in sub-Saharan Africa. The Millennium Declaration and increased development assistance for health might have been a factor in faster decreases in some developing countries. Without further accelerated progress, many countries in west and central Africa will still have high levels of under-5 mortality in 2030. FUNDING: Bill & Melinda Gates Foundation, US Agency for International Development.
Keywords: Child Mortality; Child, Preschool; Global Health; Humans; Infant; Infant Mortality; Infant, Newborn; Organizational Objectives; Risk Factors; Socioeconomic Factors

Genome-wide association analyses identify 18 new loci associated with serum urate concentrations. - Köttgen, Anna; Albrecht, Eva; Teumer, Alexander; Vitart, Veronique; Krumsiek, Jan; Hundertmark, Claudia; Pistis, Giorgio; Ruggiero, Daniela; O'Seaghdha, Conall M; Haller, Toomas; Yang, Qiong; Tanaka, Toshiko; et al. (Nat Genet, 2013)
Elevated serum urate concentrations can cause gout, a prevalent and painful inflammatory arthritis. By combining data from >140,000 individuals of European ancestry within the Global Urate Genetics Consortium (GUGC), we identified and replicated 28 genome-wide significant loci in association with serum urate concentrations (18 new regions in or near TRIM46, INHBB, SFMBT1, TMEM171, VEGFA, BAZ1B, PRKAG2, STC1, HNF4G, A1CF, ATXN2, UBE2Q2, IGF1R, NFAT5, MAF, HLF, ACVR1B-ACVRL1 and B3GNT4). Associations for many of the loci were of similar magnitude in individuals of non-European ancestry. We further characterized these loci for associations with gout, transcript expression and the fractional excretion of urate. Network analyses implicate the inhibins-activins signaling pathways and glucose metabolism in systemic urate control. New candidate genes for serum urate concentration highlight the importance of metabolic control of urate production and excretion, which may have implications for the treatment and prevention of gout.
Keywords: Analysis of Variance; European Continental Ancestry Group; Gene Frequency; Genetic Loci; Genome-Wide Association Study; Glucose; Gout; Humans; Inhibins; Polymorphism, Single Nucleotide; Signal Transduction; Uric Acid

Genetics of food preferences: a first view from silk road populations. - Pirastu, Nicola; Robino, Antonietta; Lanzara, Carmela; Athanasakis, Emmanouil; Esposito, Laura; Tepper, Beverly J; Gasparini, Paolo (J Food Sci, 2012)
Food preferences are the main factor driving food intake and choice. There are good reasons to suspect some genetic influence on food acceptance, not least because genetic factors are implicated in a number of factors that are likely to be related to food choice. In addition, some food dislikes show themselves early in life, before there is any evidence for aversive experiences. Although taste has been widely studied in regards of pure tastes such as bitter or sweet perception, the relationship between taste-related genes and food preferences has seldom been explored. In this work we investigated relationship of 37 taste-related genes with food preferences. The study was carried out during a scientific expedition through Caucasus and Central Asia (Silk Road) analyzing more than 400 samples from 5 different countries. A food preference questionnaire was administered to each participant and a DNA sample was obtained. Other information, such as age, sex, life style and anthropometrical measures, were also collected. We found significant associations with variants of: (1) TAS1R2 [Correction added after initial online publication on 27 Aug 2012. TAS1R3 was changed to TAS1R2.] gene and liking of Vodka (P= 1.6 × 10(-3)), white wine (P= 4.0 × 10(-4)) and lamb meat (P= 1.6 × 10(-3)); (2) PCLB2 gene and preference for Hot Tea (P= 8.0 × 10(-4)); (3) TPRV1 gene and beet liking (P= 3.8 × 10(-5)); and (4) ITPR3 gene and liking of both lamb meat (5.8 × 10(-4)) and sheep cheese (8.9×10(-4)). These findings give a new insight on a better understanding, of genetic factors influencing food preferences which is critical to the development of effective dietary interventions, especially for people that may be genetically not predisposed for liking specific nutrients.
Keywords: Adolescent; Adult; Aged; Aged, 80 and over; Azerbaijan; Child; Choice Behavior; Cohort Studies; Female; Food Habits; Food Preferences; Gene Frequency; Genotype; Georgia; Humans; Kazakhstan; Linear Models; Male; Middle Aged; Polymorphism, Single Nucleotide; Quantitative Trait Loci; Questionnaires; Tajikistan; Taste; Uzbekistan; Young Adult

Genome-wide association and functional follow-up reveals new loci for kidney function. - Pattaro, Cristian; Köttgen, Anna; Teumer, Alexander; Garnaas, Maija; Böger, Carsten A; Fuchsberger, Christian; Olden, Matthias; Chen, Ming-Huei; Tin, Adrienne; Taliun, Daniel; Li, Man; Gao, Xiaoyi; et al. (PLoS Genet, 2012)
Chronic kidney disease (CKD) is an important public health problem with a genetic component. We performed genome-wide association studies in up to 130,600 European ancestry participants overall, and stratified for key CKD risk factors. We uncovered 6 new loci in association with estimated glomerular filtration rate (eGFR), the primary clinical measure of CKD, in or near MPPED2, DDX1, SLC47A1, CDK12, CASP9, and INO80. Morpholino knockdown of mpped2 and casp9 in zebrafish embryos revealed podocyte and tubular abnormalities with altered dextran clearance, suggesting a role for these genes in renal function. By providing new insights into genes that regulate renal function, these results could further our understanding of the pathogenesis of CKD.
Keywords: African Americans; Aged; Animals; Caspase 9; Cyclin-Dependent Kinases; DEAD-box RNA Helicases; DNA Helicases; European Continental Ancestry Group; Female; Follow-Up Studies; Gene Knockdown Techniques; Genome-Wide Association Study; Glomerular Filtration Rate; Humans; Kidney; Kidney Failure, Chronic; Male; Middle Aged; Phosphoric Diester Hydrolases; Zebrafish

Genomic profiling by whole-genome single nucleotide polymorphism arrays in Wilms tumor and association with relapse. - Perotti, Daniela; Spreafico, Filippo; Torri, Federica; Gamba, Beatrice; d'Adamo, Pio; Pizzamiglio, Sara; Terenziani, Monica; Catania, Serena; Collini, Paola; Nantron, Marilina; Pession, Andrea; Bianchi, Maurizio; et al. (Genes Chromosomes Cancer, 2012)
Despite the excellent survival rate of Wilms tumor (WT) patients, only approximately one-half of children who suffer tumor recurrence reach second durable remission. This underlines the need for novel markers to optimize initial treatment. We investigated 77 tumors using Illumina 370CNV-QUAD genotyping BeadChip arrays and compared their genomic profiles to detect copy number (CN) abnormalities and allelic ratio anomalies associated with the following clinicopathological variables: relapse (yes vs. no), age at diagnosis (≤ 24 months vs. >24 months), and disease stage (low stage, I and II, vs. high stage, III and IV). We found that CN gains at chromosome region 1q21.1-q31.3 were significantly associated with relapse. Additional genetic events, including allelic imbalances at chromosome arms 1p, 1q, 3p, 3q, and 14q were also found to occur at higher frequency in relapsing tumors. Interestingly, allelic imbalances at 1p and 14q also showed a borderline association with higher tumor stages. No genetic events were found to be associated with age at diagnosis. This is the first genome wide analysis with single nucleotide polymorphism (SNP) arrays specifically investigating the role of genetic anomalies in predicting WT relapse on cases prospectively enrolled in the same clinical trial. Our study, besides confirming the role of 1q gains, identified a number of additional candidate genetic markers, warranting further molecular investigations.
Keywords: Adolescent; Allelic Imbalance; Child; Child, Preschool; Chromosome Aberrations; DNA Copy Number Variations; Female; Genetic Markers; Genetic Predisposition to Disease; Genome, Human; Genome-Wide Association Study; Humans; Infant; Kaplan-Meier Estimate; Male; Polymorphism, Single Nucleotide; Prospective Studies; Recurrence; Wilms Tumor

Gluten-dependent intestinal autoimmune response. - Korponay-Szabó, Ilma Rita; Simon-Vecsei, Zsafia; De Leo, Luigina; Not, Tarcisio (Curr Pharm Des, 2012)
Celiac disease is a multi-systemic autoimmune disease of the small bowel induced by gluten in genetically predisposed subjects. Highly specific and gluten-dependent production of auto-antibodies targeting self-proteins of the transglutaminase family occurs in the intestinal mucosa. These anti-transglutaminase antibodies are found deposited in intestinal and extra-intestinal tissue where they might exert biological effects, together with the intestinal mucosal gliadin-specific T lymphocytes. We conducted a brief review on antitransglutaminase antibodies effects, discussing their roles in the pathogenesis of several clinical manifestations of celiac disease.
Keywords: Animals; Autoantibodies; Celiac Disease; Genetic Predisposition to Disease; Gliadin; Glutens; Humans; Intestinal Mucosa; T-Lymphocytes; Transglutaminases

Gastroesophageal reflux disease at any cost: a dangerous paediatric attitude. - Taddio, Andrea; Bersanini, Chiara; Basile, Lucio; Fontana, Massimo; Ventura, Alessandro (Acta Paediatr, 2011)
Keywords: Diagnostic Errors; Gastroesophageal Reflux; Humans; Inappropriate Prescribing; Infant; Infant, Newborn; Male; Proton Pump Inhibitors; Spasms, Infantile

Gastrointestinal Foxp3 expression in normal, inflammatory and neoplastic conditions. - Villanacci, Vincenzo; Not, Tarcisio; Nascimbeni, Riccardo; Ferrara, Fortunato; Tommasini, Alberto; Manenti, Stefania; Antonelli, Elisabetta; Bassotti, Gabrio (Pathology, 2011)
BACKGROUND: Foxp3(+) regulatory T lymphocytes (T-regs) represent an important regulatory cell subset in inflammatory, preneoplastic and neoplastic conditions of the gastrointestinal tract. METHODS: Inflammatory, preneoplastic and neoplastic conditions of the gastrointestinal tract (189 cases) were studied with the evaluation of Foxp3 regulatory T cells based on immunohistochemistry. RESULTS: Few Foxp3(+) cells were found in controls and inflammatory conditions (oesophagitis, gastritis, coeliac disease, inflammatory bowel disease); in preneoplastic and neoplastic conditions the number of Foxp3(+) cells was significatively increased. CONCLUSIONS: In normal conditions the number of mucosal lymphocytes is very low throughout the gastro-intestinal tract; in active coeliac disease patients or on a gluten-free diet, only a slight increase in Foxp3(+) cells may be found. Gastrointestinal cancers are associated with higher Foxp3(+) cell proportion, compared with microscopically normal tissue and with precancerous conditions. However, it is uncertain whether the increase in these regulatory cells is a cause or a consequence of tumour progression.
Keywords: Adult; Aged; Celiac Disease; Cell Count; Disease Progression; Esophagitis; Female; Forkhead Transcription Factors; Gastric Mucosa; Gastritis; Humans; Inflammatory Bowel Diseases; Lymphocytes; Male; Middle Aged; Precancerous Conditions; Stomach Diseases; Stomach Neoplasms; Young Adult

Genetic predictors of glucocorticoid response in pediatric patients with inflammatory bowel diseases. - De Iudicibus, Sara; Stocco, Gabriele; Martelossi, Stefano; Londero, Margherita; Ebner, Egle; Pontillo, Alessandra; Lionetti, Paolo; Barabino, Arrigo; Bartoli, Fiora; Ventura, Alessandro; Decorti, Giuliana (J Clin Gastroenterol, 2011)
BACKGROUND: Glucocorticoids (GCs) are used in moderate-to-severe inflammatory bowel diseases (IBD) but their effect is often unpredictable. AIM: To determine the influence of 4 polymorphisms in the GC receptor [nuclear receptor subfamily 3, group C, member 1 (NR3C1)], interleukin-1β (IL-1β), and NACHT leucine-rich-repeat protein 1 (NALP1) genes, on the clinical response to steroids in pediatric patients with IBD. METHODS: One hundred fifty-four young IBD patients treated with GCs for at least 30 days and with a minimum follow-up of 1 year were genotyped. The polymorphisms considered are the BclI in the NR3C1 gene, C-511T in IL-1β gene, and Leu155His and rs2670660/C in NALP1 gene. Patients were grouped as responder, dependant, and resistant to GCs. The relation between GC response and the genetic polymorphisms considered was examined using univariate, multivariate, and Classification and Regression Tree (CART) analysis. RESULTS: Univariate analysis showed that BclI polymorphism was more frequent in responders compared with dependant patients (P=0.03) and with the combined dependant and resistant groups (P=0.02). Moreover, the NALP1 Leu155His polymorphism was less frequent in the GC responsive group compared with resistant (P=0.0059) and nonresponder (P=0.02) groups. Multivariate analysis comparing responders and nonresponders confirmed an association between BclI mutated genotype and steroid response (P=0.030), and between NALP1 Leu155His mutant variant and nonresponders (P=0.033). An association between steroid response and male sex was also observed (P=0.034). In addition, Leu155His mutated genotype was associated with steroid resistance (P=0.034). Two CART analyses supported these findings by showing that BclI and Leu155His polymorphisms had the greatest effect on steroid response (permutation P value=0.046). The second CART analysis also identified age of disease onset and male sex as important variables affecting response. CONCLUSIONS: These results confirm that genetic and demographic factors may affect the response to GCs in young patients with IBD and strengthen the importance of studying high-order interactions for predicting response.
Keywords: Adolescent; Child; Drug Resistance; Female; Follow-Up Studies; Genotype; Glucocorticoids; Humans; Inflammatory Bowel Diseases; Male; Multivariate Analysis; Polymorphism, Genetic; Receptors, Glucocorticoid; Regression Analysis; Retrospective Studies; Sex Factors; Treatment Outcome

A genome-wide approach identifies that the aspartate metabolism pathway contributes to asparaginase sensitivity. - Chen, S-H; Yang, W; Fan, Y; Stocco, G; Crews, K R; Yang, J J; Paugh, S W; Pui, C-H; Evans, W E; Relling, M V (Leukemia, 2011)
Asparaginase is an important component for treatment of childhood acute lymphoblastic leukemia (ALL). The basis for interindividual differences in asparaginase sensitivity remains unclear. To comprehensively identify genetic variants important in the cytotoxicity of asparaginase, we used a genome-wide association approach using the HapMap lymphoblastoid cell lines (87 CEU trio members) and 54 primary ALL leukemic blast samples at diagnosis. Asparaginase sensitivity was assessed as the drug concentration necessary to inhibit 50% of growth (inhibitory concentration (IC)(50)). In CEU lines, we tested 2,390,203 single-nucleotide polymorphism (SNP) genotypes at the individual SNP (P<0.001) and gene level (P<0.05), and identified 329 SNPs representing 94 genes that were associated with asparaginase IC(50). The aspartate metabolism pathway was the most overrepresented among 199 pathways evaluated (P=8.1 × 10(-3)), with primary involvement of adenylosuccinate lyase and aspartyl-tRNA synthetase genes. We validated that SNPs in the aspartate metabolism pathway were also associated with asparaginase sensitivity in primary ALL leukemic blast samples (P=5.5 × 10(-5)). Our genome-wide interrogation of CEU cell lines and primary ALL blasts revealed that inherited genomic interindividual variation in a plausible candidate pathway can contribute to asparaginase sensitivity.
Keywords: Antineoplastic Agents; Asparaginase; Aspartic Acid; Cell Line; Genome-Wide Association Study; Humans; Multivariate Analysis; Polymorphism, Single Nucleotide; Precursor Cell Lymphoblastic Leukemia-Lymphoma

Genome-wide association study identifies six new loci influencing pulse pressure and mean arterial pressure. - Wain, Louise V; Verwoert, Germaine C; O'Reilly, Paul F; Shi, Gang; Johnson, Toby; Johnson, Andrew D; Bochud, Murielle; Rice, Kenneth M; Henneman, Peter; Smith, Albert V; Ehret, Georg B; Amin, Najaf; et al. (Nat Genet, 2011)
Numerous genetic loci have been associated with systolic blood pressure (SBP) and diastolic blood pressure (DBP) in Europeans. We now report genome-wide association studies of pulse pressure (PP) and mean arterial pressure (MAP). In discovery (N = 74,064) and follow-up studies (N = 48,607), we identified at genome-wide significance (P = 2.7 × 10(-8) to P = 2.3 × 10(-13)) four new PP loci (at 4q12 near CHIC2, 7q22.3 near PIK3CG, 8q24.12 in NOV and 11q24.3 near ADAMTS8), two new MAP loci (3p21.31 in MAP4 and 10q25.3 near ADRB1) and one locus associated with both of these traits (2q24.3 near FIGN) that has also recently been associated with SBP in east Asians. For three of the new PP loci, the estimated effect for SBP was opposite of that for DBP, in contrast to the majority of common SBP- and DBP-associated variants, which show concordant effects on both traits. These findings suggest new genetic pathways underlying blood pressure variation, some of which may differentially influence SBP and DBP.
Keywords: Arteries; Blood Pressure; Case-Control Studies; Follow-Up Studies; Genetic Loci; Genome-Wide Association Study; Humans; Hypertension; Linkage Disequilibrium; Polymorphism, Single Nucleotide

Geraniol rescues inflammation in cellular and animal models of mevalonate kinase deficiency. - Marcuzzi, Annalisa; Crovella, Sergio; Pontillo, Alessandra (In Vivo, 2011)
BACKGROUND/AIM: The inhibition of the mevalonate pathway through genetic defects such as mevalonate kinase deficiency (MKD) or pharmacological drugs such as aminobisphosphonates causes a shortage of intermediate compounds, in particular geranylgeranyl-pyrophosphate (GGPP), which is associated with the consequent augmented IL-1β release in monocytes. Considering that, due to its biochemical structure, isoprenoid geraniol enters the mevalonate pathway and may revert the genetic or pharmacological inhibition, the present study tested isoprenoid geraniol in cellular and animal MKD models obtained through the use of aminobisphosphonate pamidronate. MATERIALS AND METHODS: The effect of natural isoprenoid geraniol on bacterial induced-inflammation was evaluated in a monocytic cell line (Raw 264.7) and in Balb/c mice treated with pamidronate. RESULTS: Geraniol diminished the levels of inflammatory markers induced by pamidronate stimuli in vitro and in vivo. CONCLUSION: Geraniol may be proposed as a novel therapeutic approach for the orphan disease MKD, and may also be considered for the evaluation of possible inflammatory side-effects of aminobisphosphonates.
Keywords: Animals; Anti-Inflammatory Agents; Cell Line; Diphosphonates; Disease Models, Animal; Inflammation; Lipopolysaccharides; Mevalonate Kinase Deficiency; Mice; Mice, Inbred BALB C; Monocytes; Nitric Oxide; Terpenes

"GINEXMAL RCT: Induction of labour versus expectant management in gestational diabetes pregnancies". - Maso, Gianpaolo; Alberico, Salvatore; Wiesenfeld, Uri; Ronfani, Luca; Erenbourg, Anna; Hadar, Eran; Yogev, Yariv; Hod, Moshe (BMC Pregnancy Childbirth, 2011)
BACKGROUND: Gestational diabetes (GDM) is one of the most common complications of pregnancies affecting around 7% of women. This clinical condition is associated with an increased risk of developing fetal macrosomia and is related to a higher incidence of caesarean section in comparison to the general population. Strong evidence indicating the best management between induction of labour at term and expectant monitoring are missing. METHODS/DESIGN: Pregnant women with singleton pregnancy in vertex presentation previously diagnosed with gestational diabetes will be asked to participate in a multicenter open-label randomized controlled trial between 38+0 and 39+0 gestational weeks. Women will be recruited in the third trimester in the outpatient clinic or in the Day Assessment Unit according to local protocols. Women who opt to take part will be randomized according to induction of labour or expectant management for spontaneous delivery. Patients allocated to the induction group will be admitted to the obstetric ward and offered induction of labour via use of prostaglandins, Foley catheter or oxytocin (depending on clinical conditions). Women assigned to the expectant arm will be sent to their domicile where they will be followed up until delivery, through maternal and fetal wellbeing monitoring twice weekly. The primary study outcome is the Caesarean section (C-section) rate, whilst secondary measurements are maternal and neonatal outcomes. A total sample of 1760 women (880 each arm) will be recruited to identify a relative difference between the two arms equal to 20% in favour of induction, with concerns to C-section rate. Data will be collected until mothers and newborns discharge from the hospital. Analysis of the outcome measures will be carried out by intention to treat. DISCUSSION: The present trial will provide evidence as to whether or not, in women affected by gestational diabetes, induction of labour between 38+0 and 39+0 weeks is an effective management to ameliorate maternal and neonatal outcomes. The primary objective is to determine whether caesarean section rate could be reduced among women undergoing induction of labour, in comparison to patients allocated to expectant monitoring. The secondary objective consists of the assessment and comparison of maternal and neonatal outcomes in the two study arms. .
Keywords: Adolescent; Adult; Cesarean Section; Diabetes, Gestational; Female; Gestational Age; Humans; Intention to Treat Analysis; Labor, Induced; Patient Selection; Pregnancy; Pregnancy Outcome; Research Design; Watchful Waiting; Young Adult

Glutamine-enriched nutrition does not reduce mucosal morbidity or complications after stem-cell transplantation for childhood malignancies: a prospective randomized study. - Uderzo, Cornelio; Rebora, Paola; Marrocco, Emanuela; Varotto, Stefania; Cichello, Francesca; Bonetti, Maurizio; Maximova, Natalia; Zanon, Davide; Fagioli, Franca; Nesi, Francesca; Masetti, Riccardo; Masetti, Roberto; et al. (Transplantation, 2011)
BACKGROUND: Intravenous glutamine-enriched solution seems to be effective in posttransplant period in decreasing the severity and duration of mucositis. The aim of this randomized study was to determine the benefit of glutamine supplementation both on mucosal morbidity and in posttransplant associated complications. METHODS: Children undergoing allogeneic hematopoietic stem-cell transplantation (HSCT) for malignant hematological diseases were randomly assigned to standard total parenteral nutrition (S-TPN) or glutamine-enriched (GE)-TPN solution consisting of 0.4 g/kg/day of l-alanine-glutamine dipeptide. This treatment started on the day of HSCT and ended when the patients could orally cover more than 50% of their daily energy requirements. The severity and the rate of post-HSCT mucositis were based on World Health Organization criteria. All the analyses were conducted on intention-to-treat principle. RESULTS: One hundred twenty consecutive patients (83 men; median age, 8.1 years) were enrolled. The mean duration of treatment was 23.5 and 23 days in the two treatment arms. The mean calorie intake was 1538 kcal/d in the S-TPN group and 1512 kcal/d in GE-TPN group. All patients were well nourished before and after HSCT. Mucositis occurred in 91.4% and 91.7% of patients in S-TPN and GE-TPN arm, respectively (P=0.98). Odds ratio adjusted by type of HSCT was 0.98 (95% confidence interval, 0.26-2.63). Type and duration of analgesic treatment, clinical outcome (engraftment, graft versus host disease, early morbidity, and mortality, relapse rate up to 180 days post-HSCT) were not significantly different in the two treatment arms. CONCLUSION: GE-TPN solution does not affect mucositis and outcome in well-nourished HSCT allogeneic patients.
Keywords: Adolescent; Analgesia; Child; Child, Preschool; Double-Blind Method; Female; Glutamine; Hematopoietic Stem Cell Transplantation; Humans; Infant; Male; Mucositis; Mucous Membrane; Neoplasms; Odds Ratio; Parenteral Nutrition; Prospective Studies; Recurrence; Stem Cells; Treatment Outcome

A G to C transversion at the last nucleotide of exon 25 of the MYH9 gene results in a missense mutation rather than in a splicing defect. - Vettore, Silvia; De Rocco, Daniela; Gerber, Bernhard; Scandellari, Raffaella; Bianco, Anna Monica; Balduini, Carlo L; Pecci, Alessandro; Fabris, Fabrizio; Savoia, Anna (Eur J Med Genet, 2010)
MYH9-related disease (MYH9-RD) is a rare autosomal dominant disorder caused by mutations in MYH9, the gene encoding the heavy chain of non-muscle myosin IIA. Patients present with congenital macrothrombocytopenia and inclusion bodies in neutrophils and might develop sensorineural deafness, presenile cataract, and/or progressive nephropathy leading to end-stage renal failure. In two families with macrothrombocytopenia we identified a novel c.3485G > C mutation in the last nucleotide of exon 25. Bioinformatic tools for splice site prediction and minigene functional test predicted splicing anomalies of exon 25. However, analysis of RNA purified from patient's peripheral blood did not allowed us to detect any anomalies, suggesting that RNA processing is correct at least in this tissue. Therefore, we concluded that c.3485G > C leads to a novel missense mutation (p.Arg1162Thr) of myosin-9, which resulted to be slightly degraded in patient platelets. A precise definition of the effect of mutations is fundamental to improve our knowledge into the pathogenetic mechanisms responsible for the disease.
Keywords: Adolescent; Adult; Blood Platelets; Computational Biology; Exons; Female; Humans; Inclusion Bodies; Kidney Failure, Chronic; Molecular Motor Proteins; Mutation, Missense; Myosin Heavy Chains; Neutrophils; Nonmuscle Myosin Type IIA; Nucleotides; RNA Splicing; Thrombocytopenia

Genetic polymorphism of inosine-triphosphate-pyrophosphatase influences mercaptopurine metabolism and toxicity during treatment of acute lymphoblastic leukemia individualized for thiopurine-S-methyl-transferase status. - Stocco, Gabriele; Crews, Kristine R; Evans, William E (Expert Opin Drug Saf, 2010)
IMPORTANCE OF THE FIELD: Although genetic polymorphisms in the gene encoding human thiopurine methyltransferase (TPMT) are known to have a marked effect on mercaptopurine metabolism and toxicity, there are many patients with wild-type TPMT who develop toxicity. Furthermore, when mercaptopurine dosages are adjusted in patients who are heterozygous at the TPMT locus, there are still some patients who develop toxicity for reasons that are not fully understood. Therefore, we recently studied the effects of a common polymorphism in another gene encoding an enzyme involved in mercaptopurine metabolism (SNP rs1127354 in inosine-triphospate-pyrophosphatase, ITPA), showing that genetic polymorphism of ITPA is a significant determinant of mercaptopurine metabolism and of febrile neutropenia following combination chemotherapy of acute lymphoblastic leukemia (ALL) in which mercaptopurine doses are individualized based on TPMT genotype. AREA COVERED IN THIS REVIEW: In this review, we summarize the knowledge available about the effect and clinical relevance of TPMT and ITPA on mercaptopurine pharmacogenomics, with a particular focus on the use of this medication in pediatric patients with ALL. WHAT THE READER WILL GAIN: Reader will gain insights into: i) the effects of pharmacogenomic traits on mercaptopurine toxicity and efficacy for the treatment of ALL and ii) individualization strategies that can be used to mitigate toxicity without compromising efficacy in pediatric patients with ALL. TAKE HOME MESSAGE: Mercaptopurine dose can be adjusted on the basis of TPMT genotype to mitigate toxicity in pediatric patients with ALL. As treatment is individualized in this way for the most relevant genetic determinant of drug response (i.e., for mercaptopurine, TPMT), the importance of other genetic polymorphisms emerges (e.g., ITPA).
Keywords: 6-Mercaptopurine; Antineoplastic Combined Chemotherapy Protocols; Child; Humans; Individualized Medicine; Methyltransferases; Models, Biological; Neutropenia; Nucleotide Transport Proteins; Polymorphism, Genetic; Precursor Cell Lymphoblastic Leukemia-Lymphoma; Pyrophosphatases

Gestational diabetes and fetal growth acceleration: induction of labour versus expectant management. - Alberico, S; Businelli, C; Wiesenfeld, U; Erenbourg, A; Maso, G; Piccoli, M; Ronfani, L (Minerva Ginecol, 2010)
AIM: The aim of the study was to compare elective induction of labour at 38 weeks versus expectant management in A1 and A2 gestational diabetes (GDM) pregnancies with fetal growth acceleration. Primary outcome of the study was C-section (CS) rate, while secondary outcomes were macrosomia incidence and adverse perinatal outcomes. METHODS: A retrospective cohort study was carried out. Data were collected between 1996 and 2006 and evaluated through patients' records analysis. Differences between the two study groups were investigated using non-parametric tests for continuous variables and χ2 test for categorical ones. RESULTS: There was no significant difference between induction and expectant management in terms of caesarean section rate. A trend favoring women in the induction group in terms of incidence of macrosomia and neonatal outcomes was identified, but results were not statistically significant. CONCLUSION: Labour induction at 38 weeks in GDM patients with fetal growth acceleration does not seem to determine an increased incidence of C-section in comparison to expectant management, particularly in case of maternal obesity.
Keywords: Adult; Body Mass Index; Cesarean Section; Diabetes, Gestational; Elective Surgical Procedures; Female; Fetal Development; Fetal Macrosomia; Gestational Age; Humans; Incidence; Infant, Newborn; Italy; Labor, Induced; Medical Records; Obesity; Pregnancy; Pregnancy Outcome; Retrospective Studies; Risk Factors; Statistics, Nonparametric; Watchful Waiting